High‐frequency temperature monitoring with time‐resolved wavelet analysis reveals unrecognized complexities across depth on a coral reef ecosystem - Aubrey Foulk; Tarik Gouhier; James Leichter; Alex S. J. Wyatt; Randi Rotjan; Mark Patterson; Brian Helmuth (Limnology and Oceanography, 2026)
Temperature variation at fine scales of minutes to hours and ~ 1–100 m is ubiquitous in marine ecosystems and often exceeds variability at larger scales. However, we know little of how well temperatures at one location or depth can serve as proxies to represent other locations, which is important in predicting thermal patterns relevant to organismal thermal stress. We used small data loggers to record fine‐scale temporal variability in water temperature across a depth gradient, over multiple years, on the barrier reef system in Belize. Using pairwise correlation and wavelet coherence, which quantifies the time‐ and frequency‐resolved correlation between pairs of time series, we examine how water temperature varies across reef zones (backreef, forereef inner, and forereef outer) and depths, and estimate the coherence of this variability across time scales. Although spectral analysis across the entire study period suggested a high degree of similarity in temperature patterns, time‐resolved wavelet analyses at daily, weekly, and monthly periodicities revealed significant differences across reef‐zone‐by‐depth combinations. We also detected a signal consistent with the Madden–Julian Oscillation. Coherence and phase locking at biologically relevant periodicities diminished with increasing depth difference between sites, suggesting that patterns at depth were not predictable from those near the surface. Overall, our findings show that wavelet analysis can reveal fine‐scale thermal variation on coral reefs that coarser sampling misses, and they make clear that accurately predicting how organismal performance will shift in space and time under global change depends on collecting and analyzing depth‐resolved, high‐frequency, in situ data wherever possible.

The Otway shallow fault experiment: Insights from surface monitoring - Claire Patterson; Andrew Zammit-Mangion; Ziqiu Xue; Kexin Zhang; Zibo Zhou; Wendy Timms; Andrew J. Feitz (International Journal of Greenhouse Gas Control, 2026)

Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

Acorn woodpeckers alter resource use, group size, and spring productivity across an urban landscape - Olivia R. Knapp; Kendra E. Forster; Alexander J. Rurik; Isabelle Hugoniot; Eric S. Reyes; Peter B. Schramm; Corban A. Muthiah; Aaron Wong; Seth C. Wilmoth; Sophia L. McRae; Caleb Courson; Theodore J. Patterson; et al. (Urban Ecosystems, 2026)
Access to suitable resources shapes the evolution and maintenance of avian cooperative breeding by influencing whether an individual will have a greater chance of survival and reproduction by dispersing or remaining on a natal territory. Cooperatively-breeding species exhibit altered dispersal according to food availability and habitat quality, but the relationship between resource use, group size, and reproduction in human-altered landscapes remains to be studied. We examined how urbanization, key resource availability, and resource use relate to differences in group size and number of offspring in an urban population of facultative cooperatively-breeding acorn woodpeckers. Acorn woodpeckers shifted to increased use of ornamental trees, palms, and anthropogenic structures for granaries in more urbanized areas and where oak trees, a key historic food and granary resource, are in lower abundance and proximity. Pair breeding was more prevalent in urbanized areas and seemed to be primarily associated with use of utility poles for granaries. In general, territories with utility poles as granaries and higher urbanization levels hosted smaller group sizes. In contrast, while the number of fledglings was higher in larger groups, it did not vary with urban resources when controlling for group size. Our findings suggest that land conversion levels and the relative availability of historic and novel resources shape habitat quality, resulting in differing patterns of group living and subsequent productivity across the urban landscape. This indicates that while novel resources may enable wildlife to occupy urban areas, they may also influence the social behavior of facultative cooperative breeders.

Unified framework to detect and assess behavioral shifts along the exploration-exploitation continuum: Case study of translocated bighorn sheep - Dylan G. Stewart; Autumn D. Patterson; Jonathan A. Jenks; John T. Kanta; Chadwick P. Lehman; Teresa J. Frink; Ty J. Werdel (Biological Conservation, 2026)

United States stakeholder insights on genetic testing for equine health and breeding - Michael J. Mienaltowski; Sarah Hernandez; Emma Nastrini; Carissa L. Wickens; Molly E. McCue; Laura Patterson Rosa; Elaine M. Norton; Annette M. McCoy; Samantha A. Brooks (Journal of Equine Veterinary Science, 2026)

An inventory of surficial mafic rock resources for ex-situ carbon mineralization - L.A. Thompson; A. Sjolund; J. Patterson; T. Wilson; J.L. Wade (International Journal of Greenhouse Gas Control, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Multi‐Decadal Changes in Co‐Occurrence of Migrating Landbirds Are Associated With Species‐Specific Changes in Phenology and Abundance - Joely G. DeSimone; Evan Dalton; Lucas W. DeGroote; Matthew Fuirst; Sara R. Morris; Andrea J. Patterson; Emily B. Cohen (Global Change Biology, 2025)
Human‐induced changes to the climate and environment have precipitated dramatic declines in abundance and shifts in plant and animal phenologies. These changes have been especially pronounced for migratory species that rely on numerous geographic locations throughout the year. Migratory bird species are notable in the number of species that have experienced both declines in abundance and shifts in phenology over the past 50 years, although the magnitude and direction of changes vary considerably across species. The community‐level impacts of species declines and phenological shifts have been explored in stationary communities, but we know little about the effects of these changes on species relationships during migration seasons when species may interact in ways that influence their route, timing, or success of the journey (e.g., through competition or access to information about resources). Therefore, we assessed the extent to which co‐migrating bird communities have changed over time, and whether changes in species co‐occurrence are associated with changes in abundance or shifts in migration timing. We used over 700,000 records of birds captured at five long‐term migration monitoring stations in eastern North America and found that pairwise species co‐occurrences have changed by as much as 40% over the past 50 years. Changes in co‐occurrence were consistently associated with species‐specific changes in phenology and sometimes associated with changes in abundance. Overall, stopover communities at three sites have significantly changed over the past few decades. Numerous and dramatic changes in co‐occurrence could be affecting the types and frequencies of interspecific interactions like competition and the exchange of social information, transforming the journeys of migratory birds in innumerable ways that could be altering their timing, energy, and safety.

Exploring Breastfeeding Professionals’ Perspectives on Artificial Intelligence for Breastfeeding Support - C. Tranchina; A. MacMillan Uribe; S. Econie; H. Jetel; J. Patterson (Journal of the Academy of Nutrition and Dietetics, 2025)

Evaluating Informational Quality of AI-bot Generated Outputs for Common Breastfeeding Questions - H. Jetel; J. Patterson; C. Tranchina; S. Econie; A. MacMillan Uribe (Journal of the Academy of Nutrition and Dietetics, 2025)

Comprehensibility of Artificial Intelligence Chatbot Responses for Common Breastfeeding Questions - S. Econie; A. MacMillan Uribe; H. Jetel; C. Tranchina; J. Patterson (Journal of the Academy of Nutrition and Dietetics, 2025)

Edible Campus: Empowering Students Through Integrated Campus Gardening and Meal Preparation Programs - J. Lefaver; C. Starr; D. Folliard; B. Flower; J. Patterson; M. Duffrin (Journal of the Academy of Nutrition and Dietetics, 2025)

Satellite tracking reveals sex-specific differences in the geographical and vertical habitat use of Whale sharks, Rhincodon typus, in the Eastern Indian ocean - Colby J. Bignell; Toby A. Patterson; Anthea Donovan; Mathew A. Vanderklift; Wayne Rochester; Jayson M. Semmens; Richard D. Pillans (Marine Biology, 2025)
Satellite tagging of whale sharks ( Rhincodon typus) has typically focused on juvenile males which dominate coastal aggregation sites, with limited data on the movements of females. We satellite-tagged 39 whale sharks of 3.75–9.27 m total length at Ningaloo reef between 2015 and 2018 with a roughly equivalent sex ratio (Male = 20, Female = 18, Unknown = 1).We aimed to identify differences in horizontal and vertical movements between the sexes using state-space models, kernel utilisation distributions (KUDs) and generalised additive models (GAMs). Deployment spans ranged from 9 to 340 days (mean = 132.4 ± SE = 17.9 days, N = 35) and 22 tracks exceeded 1000 km in length (mean = 2557 ± SE = 370 km, N = 35). Whale sharks spent > 90% of time in epipelagic waters ≤ 200 m and dived to a maximum depth of 1906 m. Sex-specific differences in horizontal and vertical movements were related to distinct temperature preferences. Females spent more time in offshore waters and preferred cooler Sea Surface Temperatures (SST) than males. Female movements were strongly influenced by increasing SSTs with greater space and depth use, while the space and depth use of males was more consistent with SSTs < 28 °C. We found no relationships between whale shark size and their space, depth or temperature use, though most individuals were immature (< 8 m, N = 24). The results provide novel evidence of sex-specific horizontal and vertical movements over broad geographical scales, extending current knowledge on the movement ecology and sex-specific demography of this endangered species.

Spatiotemporal drivers of water quality and phytoplankton communities in a cyanobacteria-dominated reservoir provide management insights - Linnea A. Rock; William W. Fetzer; Lindsay S. Patterson; Samuel J. Sillen; Ron Steg; Annika W. Walters; Sarah M. Collins (Environmental Monitoring and Assessment, 2025)
Reservoirs serve critical roles providing drinking water, irrigation, flood control, hydropower, recreation, fisheries, and aquatic habitat. Yet their physical position, complex shape, and large watersheds make reservoirs especially susceptible to eutrophication and harmful algal bloom (HAB) production. Boysen Reservoir, WY, is a high priority for proactive nutrient management because it is an important source for drinking water and recreation, and has a history of toxic cyanobacterial blooms. We combined four years of comprehensive monitoring efforts by state and federal agencies to characterize the spatiotemporal patterns of nutrient inflow, internal water quality dynamics, and phytoplankton community shifts in Boysen Reservoir. We found nutrient inflow was hydrologically driven, with snowmelt runoff transporting high nutrient loads. Our findings suggest physicochemical and nutrient conditions of the reservoir were strongly different between the furthest reaches of the reservoir, but less variable among the intermediate sites. Space did not play a role in phytoplankton community dynamics, but time was an important factor. Cyanobacteria dominated phytoplankton communities by mid-summer across the reservoir and were driven mainly by temporal physicochemical conditions, like stratification and water temperature. The two most dominant phytoplankton taxa across the four years of sampling were N-fixing, toxin producing cyanobacteria. Extensive monitoring efforts and data analyses can illuminate strategies to safeguard water resources via understanding the drivers of water quality changes and HAB production.

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

Call for neurofibromatosis specialty care clinics in South Carolina - Camerun C. Washington; Kenya M. De Leon; Jessica A. Cooley Coleman; Wesley G. Patterson; Michael J. Lyons (Journal of Community Genetics, 2025)

The effect of local perennial plants on the occurrence and traits of the Brachypodium distachyon complex along an aridity gradient - Megan K. Korte; Antonio J. Manzaneda; Luisa M. Martinez; Tamatha A. Patterson; Rampal S. Etienne; Louis van de Zande; Christian Smit (Plant Ecology, 2025)
Plant-plant interactions are well-known drivers of plant community dynamics and plant traits. Less well known is to what extent these interactions and their effects change along stress gradients. To study this, we assessed the local spatial association of the annual grass species Brachypodium hybridum and Brachypodium distachyon to perennial plants in ten sites along an aridity gradient in southeastern Spain and compared ten phenotypic traits of Brachypodium occurring underneath and outside the perennial plant canopy. We found that Brachypodium was less associated with perennials with increasing aridity but with a significant site effect. This site effect seemed to be due to one particular site, the removal of which from our analysis resulted in an even stronger negative correlation and uncovered a significant influence of the perennial plant. We also found that while overall three phenotypic traits (plant height, spike length, and seed number) were different between plants underneath perennial plants and plants outside perennials, only one of these differences (spike length) changed significantly along the gradient. Further, in controlled conditions, we found that the offspring of annual plants collected from outside perennial plant canopies in the least arid site flowered more rapidly than those from underneath perennial plants, but this difference was not observed for the most arid site. These results indicate that in patchy arid landscapes dominated by perennial plants, Brachypodium ’s response to the microhabitat provided by neighboring perennial plants changes along the aridity gradient, but other factors such as site and perennial plant may counteract or strengthen the effects of aridity.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Relationship Between Diet Quality and 21-Year Cumulative Health Care Costs Among Australian Women: A Longitudinal Cohort Study - Erin D. Clarke; Jennifer N. Cartwright; Lee M. Ashton; Tracy L. Burrows; Alexis Hure; Deborah Loxton; Amanda J. Patterson; Clare E. Collins (Journal of the Academy of Nutrition and Dietetics, 2025)

Ontogenetic change in body shape for white sharks, Carcharodon carcharias , in Australian waters - Emily Hunt; Russell W. Bradford; David J. Booth; Cameron Doak; Toby A. Patterson; Victor M. Peddemors (Journal of Fish Biology, 2025)
The analysis of how biological shape changes across ontogeny can provide us with valuable information on how species adapt behaviorally, physiologically, and ecologically. The white shark Carcharodon carcharias is one of the largest and most widely distributed apex predators globally, yet an understanding of ontogenetic changes in body shape and relative scaling of length and weight measures is limited, especially in relation to foraging ecology. Through analysis of a suite of shape‐related metrics, we identified ontogenetic patterns of scaling throughout development. Isometric growth was exhibited for most metrics, failing to show a significant deviation from an isometric slope of 1.0 for length–length relationships, and 3.0 for weight–length relationships. The most notable difference from this trend was the negative allometric growth observed for the upper caudal‐fin lobe length, trunk length, and the mouth length. The surface area of the fins also presented a strong, positive relationship with precaudal length (PCL) and the girth at the pectoral fin. Negative allometric growth was exhibited for three of the fins (pectoral, upper caudal fin, and lower caudal fin) against PCL, exhibiting a significant deviation from the expected isometric growth of 2.0 for area–length relationships. There were no significant differences in morphometric relationships between geographic regions within Australia that samples were collected from. No differences between the sexes were identified; however, this may be an artifact of the lack of mature animal samples. Conversely, life stage was found to have a significant effect on the girth–length and weight–length relationships. The development of regression equations for morphometric measures allows the assessment of white shark body condition and may serve as an assessment tool to understand the potential impacts of human‐induced environmental change on white sharks.

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

The effects of exercise, heat-induced hypo-hydration and rehydration on blood–brain-barrier permeability, corticospinal and peripheral excitability - Nasir Uddin; Jamie Scott; Jonathan Nixon; Stephen D. Patterson; Dawson Kidgell; Alan J. Pearce; Mark Waldron; Jamie Tallent (European Journal of Applied Physiology, 2025)
Purpose The effects of low-intensity exercise, heat-induced hypo-hydration and rehydration on maximal strength and the underlying neurophysiological mechanisms are not well understood. Methods To assess this, 12 participants took part in a randomised crossover study, in a prolonged (3 h) submaximal (60 W) cycling protocol under 3 conditions: (i) in 45 °C (achieving ~ 5% body mass reduction), with post-exercise rehydration in 2 h (RHY2), (ii) with rehydration across 24 h (RHY24), and (iii) a euhydrated trial in 25 °C (CON). Dependent variables included maximal voluntary contractions (MVC), maximum motor unit potential (M MAX ), motor evoked potential (MEP RAW ) amplitude and cortical silent period (cSP) duration. Blood–brain-barrier integrity was also assessed by serum Ubiquitin Carboxyl-terminal Hydrolase (UCH-L1) concentrations. All measures were obtained immediately pre, post, post 2 h and 24 h. Results During both dehydration trials, MVC (RHY2: p < 0.001, RHY24: p = 0.001) and MEP RAW (RHY2: p = 0.025, RHY24: p = 0.045) decreased from pre- to post-exercise. MEP RAW returned to baseline during RHY2 and CON, but not RHY24 ( p = 0.020). MEP/M MAX ratio decreased across time for all trials ( p = 0.009) and returned to baseline, except RHY24 ( p < 0.026). Increased cSP ( p = 0.011) was observed during CON post-exercise, but not during RHY2 and RHY24. Serum UCH-L1 increased across time for all conditions ( p < 0.001) but was not significantly different between conditions. Conclusion Our findings demonstrate an increase in corticospinal inhibition after exercise with fluid ingestion, but a decrease in corticospinal excitability after heat-induced hypo-hydration. In addition, low-intensity exercise increases peripheral markers of blood–brain-barrier permeability. Graphical abstract

Spatiotemporal dynamics and habitat use of red snapper (Lutjanus campechanus) on the southeastern United States Atlantic continental shelf - Nathan M. Bacheler; William F. Patterson III; Joseph H. Tarnecki; Kyle W. Shertzer; Jeffrey A. Buckel; Nathan J. Hostetter; Krishna Pacifici; Viviane Zulian; Walter J. Bubley (Fisheries Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Organic matter is a predominant control on total mercury concentration of near-surface lake sediments across a boreal to low Arctic tundra transect in northern Canada - Jennifer M. Galloway; Michael B. Parsons; Omid H. Ardakani; Hendrik Falck; Richard E. Fewster; Graeme T. Swindles; Hamed Sanei; Michael J. Palmer; Nawaf A. Nasser; R. Timothy Patterson (Science of The Total Environment, 2024)

Immune gene regulation is associated with age and environmental adversity in a nonhuman primate - Marina M. Watowich; Christina E. Costa; Kenneth L. Chiou; Elisabeth A. Goldman; Rachel M. Petersen; Sam Patterson; Melween I. Martínez; Kirstin N. Sterner; Julie E. Horvath; Michael J. Montague; Michael L. Platt; Lauren J. N. Brent; et al. (Molecular Ecology, 2024)
Phenotypic aging is ubiquitous across mammalian species, suggesting shared underlying mechanisms of aging. Aging is linked to molecular changes to DNA methylation and gene expression, and environmental factors, such as severe external challenges or adversities, can moderate these age‐related changes. Yet, it remains unclear whether environmental adversities affect gene regulation via the same molecular pathways as chronological, or ‘primary’, aging. Investigating molecular aging in naturalistic animal populations can fill this gap by providing insight into shared molecular mechanisms of aging and the effects of a greater diversity of environmental adversities – particularly those that can be challenging to study in humans or laboratory organisms. Here, we characterised molecular aging – specifically, CpG methylation – in a sample of free‐ranging rhesus macaques living off the coast of Puerto Rico ( n samples = 571, n individuals = 499), which endured a major hurricane during our study. Age was associated with methylation at 78,661 sites (31% of all sites tested). Age‐associated hypermethylation occurred more frequently in areas of active gene regulation, while hypomethylation was enriched in regions that show less activity in immune cells, suggesting these regions may become de‐repressed in older individuals. Age‐associated hypomethylation also co‐occurred with increased chromatin accessibility while hypermethylation showed the opposite trend, hinting at a coordinated, multi‐level loss of epigenetic stability during aging. We detected 32,048 CpG sites significantly associated with exposure to a hurricane, and these sites overlapped age‐associated sites, most strongly in regulatory regions and most weakly in quiescent regions. Together, our results suggest that environmental adversity may contribute to aging‐related molecular phenotypes in regions of active gene transcription, but that primary aging has specific signatures in non‐regulatory regions.

Cultivating Care: A Workshop to Identify and Support Students with Disordered Eating Patterns - G. Molina; J. Patterson; M. Duffrin; T. Miralaeff; K. Lockwood (Journal of the Academy of Nutrition and Dietetics, 2024)

Longitudinal neuroanatomical increases from early to one-year postpartum - Alexander J. Dufford; Genevieve Patterson; Pilyoung Kim (Brain Structure and Function, 2024)

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Effects of an enzyme mixture supplementation on energy and nutrient digestibility in soybean expellers fed to growing pigs - J. Song; A. Aljuobori; R. Patterson; C.M. Nyachoti (Animal Feed Science and Technology, 2024)

The effect of urbanization and behavioral factors on coyote net displacement and its implications for seed dispersal - Tiziana A. Gelmi-Candusso; Tyler J. Wheeldon; Brent R. Patterson; Marie-Josée Fortin (Urban Ecosystems, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Estimating reductions in the risk of vessels striking whales achieved by management strategies - Jessica V. Redfern; Brooke C. Hodge; Daniel E. Pendleton; Amy R. Knowlton; Jeffrey Adams; Eric M. Patterson; Caroline P. Good; Jason J. Roberts (Biological Conservation, 2024)

Implications of changing Caribbean coral reefs on Diadema antillarum larvae settlement - Tom Wijers; Britt van Herpen; Djan Mattijssen; Albertinka J. Murk; Joshua T. Patterson; Alwin Hylkema (Marine Biology, 2024)
Tropical western Atlantic reefs have gradually shifted from being dominated by corals to being mainly covered by macroalgae. The mass-mortality of the sea urchin Diadema antillarum in the 80s and the slow to non-existent recovery exacerbated this shift. Chemical cues associated with these reefs are expected to have shifted too with potential negative effects on larval recruitment, possibly limiting recovery of important species like D. antillarum . In this study, we tested the effects of naturally derived biofilm and macroalgae species native to Caribbean coral reefs on the settlement rate of cultured D. antillarum larvae in two separate experiments. Crustose coralline algae (CCA) were included in both experiments, making it possible to compare settlement rates from both experiments. A biofilm of one week old yielded significantly lower settlement rates compared to two, four, and six weeks old biofilm and the highest settlement rate was found for CCA with over 62% of total larvae. All six tested macroalgae species resulted in settled larvae, with little significant difference between algal species, partly due to a high variation in settlement rates within treatments. Sargassum fluitans induced the highest settlement rate with 33%, which was not significantly different from CCA with 29%. We conclude that dominant macroalgae species likely to be encountered by D. antillarum on shifted reefs are no major constraint to settlement. Our findings increase the understanding of alternative stable state settlement dynamics for a keystone coral reef herbivore.

Quantifying conditions required for varve formation in meromictic Crawford Lake, Ontario, Canada: important process for delimiting the Anthropocene epoch - Brendan M. Llew-Williams; Francine M. G. McCarthy; Andrea M. Krueger; Nicholas L. Riddick; Michael D. MacKinnon; Krysten M. Lafond; R. Timothy Patterson; Nawaf A. Nasser; Martin J. Head; Michael F. J. Pisaric; Kevin W. Turner; Joseph I. Boyce; et al. (Journal of Paleolimnology, 2024)

Contaminated sediment in the Detroit River provokes acclimated responses in wild brown bullhead (Ameiurus nebulosus) populations - J. Assad; S. Cho; V. Dileo; G. Gascoigne; A.V. Hubberstey; D. Patterson; R. Williams (Aquatic Toxicology, 2023)

Response to Podgorski and Bekins's comments on Zemo et al. (2022) - Kirk T. O'Reilly; Timothy J. Patterson; Dawn A. Zemo; Rachel E. Mohler (Aquatic Toxicology, 2023)

Holocene climate change shifted Southern Ocean biogeochemical cycling and predator trophic dynamics - Chantel I. Michelson; Michael J. Polito; Michael B. Wunder; Steven D. Emslie; Matthew D. McCarthy; William P. Patterson; Kelton W. McMahon (Limnology and Oceanography, 2023)
Studies of Antarctic paleo‐archives have produced conflicting hypotheses on the relative impact of long‐term climate change and historic exploitation of marine mammals on Southern Ocean krill predator foraging ecology. We disentangle these hypotheses using amino acid stable isotope analysis on a 7000‐yr Holocene archive of Adélie penguin ( Pygoscelis adeliae ) eggshells to differentiate variation in diet and trophic dynamics from baseline biogeochemical cycling as drivers of the rapid decline in krill predator bulk tissue δ 15 N values in recent centuries. Contrary to previous hypotheses suggesting solely trophic dynamic mechanisms as drivers of this decline, we identified an abrupt decline in source amino acid δ 15 N values, indicative of major changes in biogeochemical cycling at the base of the Southern Ocean food web that mirrored the decline in penguin bulk tissue δ 15 N values. These abrupt shifts in penguin δ 15 N values and associated biogeochemical cycling aligned with climatic events during the Little Ice Age that decreased surface δ 15 N NO3− , likely connected to a proposed increase in Ekman upwelling via a southward migration of the Westerlies. This baseline shift was in addition to a long‐term, gradual decline in penguin trophic position over the Holocene that began prior to both recent anthropogenic climate change and a proposed “krill‐surplus” following historic marine mammal exploitation in the 19 th and 20 th centuries. In resolving these outstanding hypotheses about drivers of Southern Ocean food web dynamics, this study emphasizes the fundamental importance of climate‐induced variability in biogeochemical cycling on ecological processes and improves the ability of paleo‐archives to inform the ecological consequences of future environmental change in the Southern Ocean.

Wastewater-based surveillance can be used to model COVID-19-associated workforce absenteeism - Nicole Acosta; Xiaotian Dai; Maria A. Bautista; Barbara J. Waddell; Jangwoo Lee; Kristine Du; Janine McCalder; Puja Pradhan; Chloe Papparis; Xuewen Lu; Thierry Chekouo; Alexander Krusina; et al. (Science of The Total Environment, 2023)

Anaerobic Exercise and Recovery: Roles and Implications for Mortality in Pacific Salmon - Kim Birnie-Gauvin; David A. Patterson; Steven J. Cooke; Scott G. Hinch; Erika J. Eliason (Reviews in Fisheries Science & Aquaculture, 2023)

Automated remote sensing tools to counter illicit maritime activity: vessel detection, bathymetry and topography from WorldView imagery - Matthew J. McCarthy; David Hughes; Jeremy Patterson; Michael A. Channer; Michael McGee; Shannon Meade; Kenny Moss; Paul Trask (International Journal of Remote Sensing, 2023)

Using repeat injury assessments in adult sockeye salmon (Oncorhynchus nerka) to predict spawning success and describe severity of migration conditions - Madison A. Philipp; Kathryn S. Peiman; Glenn T. Crossin; Scott G. Hinch; David A. Patterson; Chris K. Elvidge; Steven J. Cooke (Fisheries Research, 2023)

The Effects of Weight Bias Internalization on Disordered Eating, Dieting, and Intuitive Eating in College Students - S. Tietje; H. Muzaffar; T. Smith; J. Patterson; J. Lukaszuk (Journal of the Academy of Nutrition and Dietetics, 2023)

Examination of Food Allergy Accommodations and Barriers for College Campus Dining Services - K. Stawarz; J. Lukaszuk; J. Patterson; H. Muzaffar; W. Pitney (Journal of the Academy of Nutrition and Dietetics, 2023)

Two new species of the genus Leptomyxa (Goodey, 1915) – Leptomyxa botanica n. sp. and Leptomyxa monrepos n. sp. from the soil habitats of Northwestern Russia - Nikita S. Kulishkin; Alexey V. Smirnov; David J. Patterson (European Journal of Protistology, 2023)

Description of a new species in the genus Sarcothelia Verrill, 1928 (Alcyonacea: Xeniidae) from reefs of Gulf of Mannar, South-eastern India - Mahalakshmi Boopathi; Angelo Poliseno; Alvaro Altuna; J. K. Patterson Edward (Marine Biodiversity, 2023)

Evidence of population-level impacts and resiliency for Gulf of Mexico shelf taxa following the Deepwater Horizon oil spill - William F. Patterson; Kelly Lynn Robinson; Beverly K. Barnett; Matthew D. Campbell; David C. Chagaris; Jeffrey P. Chanton; Kendra L. Daly; David S. Hanisko; Frank J. Hernandez; Steven A. Murawski; Adam G. Pollack; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The goal of this paper was to review the evidence of population-level impacts of the Deepwater Horizon Oil Spill (DWH) on Gulf of Mexico (GOM) continental shelf taxa, as well as evidence of resiliency following the DWH. There is considerable environmental and biological evidence that GOM shelf taxa were exposed to and suffered direct and indirect impacts of the DWH. Numerous assessments, from mesocosm studies to analysis of biopsied tissue or tissue samples from necropsied animals, revealed a constellation of physiological effects related to DWH impacts on GOM biota, some of which clearly or likely resulted in mortality. While the estimated concentrations of hydrocarbons in shelf waters and sediments were orders of magnitude lower than measured in inshore or deep GOM environments, the level of mortality observed or predicted was substantial for many shelf taxa. In some cases, such as for zooplankton, community shifts following the spill were ephemeral, likely reflecting high rates of population turnover and productivity. In other taxa, such as GOM reef fishes, impacts of the spill are confounded with other stressors, such as fishing mortality or the appearance and rapid population growth of invasive lionfish ( Pterois spp.). In yet others, such as cetaceans, modeling efforts to predict population-level effects of the DWH made conservative assumptions given the species’ protected status, which post-DWH population assessments either failed to detect or population increases were estimated. A persistent theme that emerged was the lack of precise population-level data or assessments prior to the DWH for many taxa, but even when data or assessments did exist, examining evidence of population resiliency was confounded by other stressors impacting GOM biota. Unless efforts are made to increase the resolution of the data or precision of population assessments, difficulties will likely remain in estimating the scale of population-level effects or resiliency in the case of future large-scale environmental catastrophes.

Evaluation of Zoetis GeneMax Advantage genomic predictions in commercial Bos taurus Angus cattle - Brian.C. Arisman; Troy N. Rowan; Jordan M. Thomas; Harly J. Durbin; William R. Lamberson; David J. Patterson; Jared E. Decker (Livestock Science, 2023)

Metabolic constraints and individual variation shape the trade‐off between physiological recovery and anti‐predator responses in adult sockeye salmon - Michael J. Lawrence; Tanya S. Prystay; Melissa Dick; Erika J. Eliason; Chris K. Elvidge; Scott G. Hinch; David A. Patterson; Andrew G. Lotto; Steven J. Cooke (Journal of Fish Biology, 2023)
Metabolic scope represents the aerobic energy budget available to an organism to perform non‐maintenance activities ( e.g. , escape a predator, recover from a fisheries interaction, compete for a mate). Conflicting energetic requirements can give rise to ecologically relevant metabolic trade‐offs when energy budgeting is constrained. The objective of this study was to investigate how aerobic energy is utilized when individual sockeye salmon ( Oncorhynchus nerka ) are exposed to multiple acute stressors. To indirectly assess metabolic changes in free‐swimming individuals, salmon were implanted with heart rate biologgers. The animals were then exercised to exhaustion or briefly handled as a control, and allowed to recover from this stressor for 48 h. During the first 2 h of the recovery period, individual salmon were exposed to 90 ml of conspecific alarm cues or water as a control. Heart rate was recorded throughout the recovery period. Recovery effort and time was higher in exercised fish, relative to control fish, whereas exposure to an alarm cue had no effect on either of these metrics. Individual routine heart rate was negatively correlated with recovery time and effort. Together, these findings suggest that metabolic energy allocation towards exercise recovery ( i.e. , an acute stressor; handling, chase, etc. ) trumps anti‐predator responses in salmon, although individual variation may mediate this effect at the population level.

Phylogeography of the Asian green mussel, Perna viridis: pronounced regional genetic differentiation is explained by major freshwater input into the Bay of Bengal - Jonathan P. A. Gardner; Jamila Patterson; Edward J. K. Patterson (Frontiers in Marine Science, 2023)
The Asian green mussel (AGM), Perna viridis , is a mussel of ecological and economic importance throughout much of the tropical and subtropical regions of Asia, from China and Korea in the east to Oman on the Arabian Peninsula in the west. We collated published DNA sequence data and then analysed 467 bp of cytochrome c oxidase I gene (COI) sequence variation from 649 mussels (576 from SE Asia and 73 from India) to test for regional differentiation. Analysis of molecular variation, a haplotype network and a neighbour-joining tree all revealed significant differentiation between mussels from India and those from SE Asia. We observed a greater number of segregating sites (haplotypes) and private haplotypes than expected for Indian mussels compared to SE Asian mussels, based on the respective sample sizes. Tests of neutrality revealed population expansion or a recent selective sweep for only the mussels from India. We suggest that the differentiation of the Indian from the SE Asian mussels is explained by the pronounced seasonal input of freshwater into the northern Bay of Bengal area, which acts as a (semi-permeable) barrier to gene flow between the two regions (i.e., east versus west of the Bay). This suggestion is based on the oceanography of the region and is consistent with the biogeography and reports of genetic breaks in a range of taxa in this region. Further targetted sampling of AGMs from the east coast of India, Bangladesh and Myanmar is required to test this hypothesis, and additional sampling of AGMs from west of India (e.g., Pakistan, Iran, the Arabian Peninsula) will also be informative. Finally, this study is based on the analysis of a single marker (COI) because this is all that is presently available from published sources but we note that the application of new molecular markers such as single nucleotide polymorphisms to newly collected mussel samples will greatly advance our understanding of the AGM genetic discontinuity and its age, and help test its geographical location and its nature (e.g., a steep/shallow cline or a stepped cline).

Evaluating the fidelity of enamel isotopic data and environmental variation in paleoecological studies: A case study in wild, known-aged, modern white-tailed deer (Odocoileus virginianus) - Taylor Malasek; Erin Barding; Michael J. Bender; Alexandra Bonham; Alfred J. Mead; Zachary Pilgrim; Patrick Powers; Jessica R. Patterson; David B. Patterson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Forecast‐ready models to support fisheries' adaptation to global variability and change - Kylie L. Scales; Thomas S. Moore; Bernadette Sloyan; Claire M. Spillman; J. Paige Eveson; Toby A. Patterson; Ashley J. Williams; Alistair J. Hobday; Jason R. Hartog (Fisheries Oceanography, 2023)
Ocean and climate drivers affect the distribution and abundance of marine life on a global scale. Marine ecological forecasting seeks to predict how living marine resources respond to physical variability and change, enabling proactive decision‐making to support climate adaptation. However, the skill of ecological forecasts is constrained by the skill of underlying models of both ocean state and species‐environment relationships. As a test of the skill of data‐driven forecasts for fisheries, we developed predictive models of catch‐per‐unit‐effort (CPUE) of tuna and billfish across the south‐west Pacific Ocean, using a 12‐year time series of catch data and a large ensemble climate reanalysis. Descriptors of water column structure, particularly temperature at depth and upper ocean heat content, emerged as useful predictors of CPUE across species. Enhancing forecast skill over sub‐seasonal to multi‐year timescales in any system is likely to require the inclusion of sub‐surface ocean data and explicit consideration of regional physical dynamics.

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Offshore decommissioning horizon scan: Research priorities to support decision-making activities for oil and gas infrastructure - Sarah M. Watson; Dianne L. McLean; Brian J. Balcom; Silvana N.R. Birchenough; Alison M. Brand; Elodie C.M. Camprasse; Jeremy T. Claisse; Joop W.P. Coolen; Tom Cresswell; Bert Fokkema; Susan Gourvenec; Lea-Anne Henry; et al. (Science of The Total Environment, 2023)

High-resolution entry and exit surface dosimetry in a 1.5 T MR-linac - E. Patterson; P. Stokes; D. Cutajar; A. Rosenfeld; J. Baines; P. Metcalfe; M. Powers (Physical and Engineering Sciences in Medicine, 2023)
The magnetic field of a transverse MR-linac alters electron trajectories as the photon beam transits through materials, causing lower doses at flat entry surfaces and increased doses at flat beam-exiting surfaces. This study investigated the response of a MOSFET detector, known as the MO Skin ™, for high-resolution surface and near-surface percentage depth dose measurements on an Elekta Unity. Simulations with Geant4 and the Monaco treatment planning system (TPS), and EBT-3 film measurements, were also performed for comparison. Measured MO Skin ™ entry surface doses, relative to D max , were (9.9 ± 0.2)%, (10.1 ± 0.3)%, (11.3 ± 0.6)%, (12.9 ± 1.0)%, and (13.4 ± 1.0)% for 1 × 1 cm 2 , 3 × 3 cm 2 , 5 × 5 cm 2 , 10 × 10 cm 2 , and 22 × 22 cm 2 fields, respectively. For the investigated fields, the maximum percent differences of Geant4, TPS, and film doses extrapolated and interpolated to a depth suitable for skin dose assessment at the beam entry, relative to MO Skin ™ measurements at an equivalent depth were 1.0%, 2.8%, and 14.3%, respectively, and at a WED of 199.67 mm at the beam exit, 3.2%, 3.7% and 5.7%, respectively. The largest measured increase in exit dose, due to the electron return effect, was 15.4% for the 10 × 10 cm 2 field size using the MO Skin ™ and 17.9% for the 22 × 22 cm 2 field size, using Geant4 calculations. The results presented in the study validate the suitability of the MO Skin ™ detector for transverse MR-linac surface dosimetry.

95 Health parameter variation in emaciated stock-type horses going through two refeeding protocols - C.L. Viana; Z. Dodson; H. Santos; J. Boyd; L. Patterson Rosa (Journal of Equine Veterinary Science, 2023)

94 Age and feeding behavior associated with dental disorders in Western horses - K.Y. Lai; N. Moore; R. Allen; H. Santos; J. Boyd; L. Patterson Rosa (Journal of Equine Veterinary Science, 2023)

A global assessment of the prevalence of current and potential future infrastructure in Key Biodiversity Areas - Ashley T. Simkins; Alison E. Beresford; Graeme M. Buchanan; Olivia Crowe; Wendy Elliott; Pablo Izquierdo; David J. Patterson; Stuart H.M. Butchart (Biological Conservation, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Advancing textural heterogeneity: Effect of manipulating multi-component model foods on the perception of textural complexity - Niamh M. Patterson; Yvonne S. Kuiper; Sophia A. Rodrigues; Bryony J. James; Nicholas Gant; Michael J. Hautus (Food Research International, 2023)

Perceptions of Freshwater Algal Blooms, Causes and Health among New Brunswick Lakefront Property Owners - Sapriya Birk; J. David Miller; Aidan MacMullin; R. Timothy Patterson; Paul J. Villeneuve (Environmental Management, 2023)

Novel shaker bottle cultivation method for the long spined sea urchin (Diadema antillarum; Philippi, 1845) results in high larval survival and settlement rates - Tom Wijers; Alwin Hylkema; Aaron R. Pilnick; Albertinka J. Murk; Joshua T. Patterson (Aquaculture, 2023)

Estimating Adult Pacific Salmon Energy Use in Coastal British Columbia and the Fraser River Estuary with Acoustic Accelerometer Transmitters - S. M. Wilson; S. G. Hinch; D. A. Patterson; E. J. Eliason; S. J. Cooke (Estuaries and Coasts, 2022)

Episodic Ataxia Type 1: Natural History and Effect on Quality of Life - Tracey D. Graves; Robert C. Griggs; Brian N. Bundy; Joanna C. Jen; Robert W. Baloh; Michael G. Hanna; Joanna J. Jen; Anthony A. Amato; Richard J. Barohn; Angelika F. Hahn; Kimberly Hart; Barbara Herr; et al. (The Cerebellum, 2022)
Episodic ataxia type 1 (EA1) is a rare autosomal potassium channelopathy, due to mutations in KCNA1 . Patients have childhood onset of intermittent attacks of ataxia, dizziness or imbalance. In order to quantify the natural history of EA1, its effect on quality of life and in preparation for future clinical trials, we set up an international multi-centre study of EA1. We recruited thirty-three participants with EA1: twenty-three completed 1-year follow-up and eighteen completed 2-year follow-up. There was very little accumulation of disability or impairment over the course of the 2 years of the study. The outcome measures of ataxia (SARA and functional rating of ataxia) and the activities of daily living scale were largely stable over time. Self-reported health-related quality of life (SF-36) scores were lower across all domains than controls, in keeping with a chronic condition. Physical subdomain scores appeared to deteriorate over time, which seems to be driven by the female participants in the study. This is an interesting finding and warrants further study. Attacks of EA1 reported by participants in real time via an interactive voice response system showed that symptoms were not stereotyped; however, attack duration and frequency was stable between individuals. This large prospective study is the first ever completed in subjects with EA1. We document the natural history of the disorder over 2 years. These data will enable the development of outcome measures for clinical trials of treatment.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Compound urban crises - Linda Westman; James Patterson; Rachel Macrorie; Christopher J. Orr; Catherine M. Ashcraft; Vanesa Castán Broto; Dana Dolan; Mukesh Gupta; Jeroen van der Heijden; Thomas Hickmann; Robert Hobbins; Marielle Papin; et al. (Ambio, 2022)
The crises that cities face—such as climate change, pandemics, economic downturn, and racism—are tightly interlinked and cannot be addressed in isolation. This paper addresses compound urban crises as a unique type of problem, in which discrete solutions that tackle each crisis independently are insufficient. Few scholarly debates address compound urban crises and there is, to date, a lack of interdisciplinary insights to inform urban governance responses. Combining ideas from complex adaptive systems and critical urban studies, we develop a set of boundary concepts (unsettlement, unevenness, and unbounding) to understand the complexities of compound urban crises from an interdisciplinary perspective. We employ these concepts to set a research agenda on compound urban crises, highlighting multiple interconnections between urban politics and global dynamics. We conclude by suggesting how these entry points provide a theoretical anchor to develop practical insights to inform and reform urban governance.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Effects of short-term decomposition on isotope values of fish tissues under natural conditions - Kathryn S. Peiman; Hsien-Yung Lin; Michael Power; Scott G. Hinch; David A. Patterson; Steven J. Cooke (Aquatic Ecology, 2022)

Using an integrative research approach to improve fish migrations in regulated rivers: a case study on Pacific Salmon in the Seton River, Canada - Nolan N. Bett; Scott G. Hinch; Arthur L. Bass; Douglas C. Braun; Nicholas J. Burnett; Matthew T. Casselman; Steven J. Cooke; S. Matthew Drenner; Ahmed Gelchu; William L. Harrower; Roxx Ledoux; Andrew G. Lotto; et al. (Hydrobiologia, 2022)

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

The impacts of climate change and post bleaching effects on the octocoral communities of Gulf of Mannar, India - Mahalakshmi Boopathi; P Dinesh Kumar; J K Patterson Edward (Journal of Earth System Science, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genomic‐based epidemiology reveals independent origins and gene flow of glyphosate resistance in Bassia scoparia populations across North America - Karl Ravet; Crystal D. Sparks; Andrea L. Dixon; Anita Küpper; Eric P. Westra; Dean J. Pettinga; Patrick J. Tranel; Joel Felix; Don W. Morishita; Prashant Jha; Andrew Kniss; Phillip W. Stahlman; et al. (Molecular Ecology, 2021)
Genomic‐based epidemiology can provide insight into the origins and spread of herbicide resistance mechanisms in weeds. We used kochia ( Bassia scoparia ) populations resistant to the herbicide glyphosate from across western North America to test the alternative hypotheses that (i) a single EPSPS gene duplication event occurred initially in the Central Great Plains and then subsequently spread to all other geographical areas now exhibiting glyphosate‐resistant kochia populations or that (ii) gene duplication occurred multiple times in independent events in a case of parallel evolution. We used qPCR markers previously developed for measuring the structure of the EPSPS tandem duplication to investigate whether all glyphosate‐resistant individuals had the same EPSPS repeat structure. We also investigated population structure using simple sequence repeat markers to determine the relatedness of kochia populations from across the Central Great Plains, Northern Plains and the Pacific Northwest. We found that the original EPSPS duplication genotype was predominant in the Central Great Plains where glyphosate resistance was first reported. We identified two additional EPSPS duplication genotypes, one having geographical associations with the Northern Plains and the other with the Pacific Northwest. The EPSPS duplication genotype from the Pacific Northwest seems likely to represent a second, independent evolutionary origin of a resistance allele. We found evidence of gene flow across populations and a general lack of population structure. The results support at least two independent evolutionary origins of glyphosate resistance in kochia, followed by substantial and mostly geographically localized gene flow to spread the resistance alleles into diverse genetic backgrounds.

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Residency, home range and tidal habitat use of Green Turtles (Chelonia mydas) in Port Curtis, Australia - Richard D. Pillans; Gary C. Fry; Michael D. E. Haywood; Wayne Rochester; Colin J. Limpus; Toby Patterson; Russel C. Babcock (Marine Biology, 2021)

Determining effective acoustic array design for monitoring presence of white sharks Carcharodon carcharias in nearshore habitats - Sofia M. Gabriel; T. A. Patterson; J. P. Eveson; J. M. Semmens; D. Harasti; P. A. Butcher; J. L. Y. Spaet; R. W. Bradford (Marine Biology, 2021)

Dredging Impacts on Soil Properties of the Kankakee River System 150 Years after Perturbation - Jack V. Ferrara; Joshua J. Puhlick; Tamatha A. Patterson; Katherine C. Glover (Wetlands, 2020)

A Hope-Based Intervention to Address Disrupted Goal Pursuits and Quality of Life Among Young Adult Cancer Survivors - Carla J. Berg; Robin C. Vanderpool; Betelihem Getachew; Jackelyn B. Payne; Meghan F. Johnson; Yasmeni Sandridge; Jennifer Bierhoff; Lana Le; Rakiyah Johnson; Amber Weber; Akilah Patterson; Sarah Dorvil; et al. (Journal of Cancer Education, 2020)

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - Russell Bradford; T. A. Patterson; P. J. Rogers; R. McAuley; S. Mountford; C. Huveneers; R. Robbins; A. Fox; B. D. Bruce (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias , between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures ( F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.

Coming to Terms With Living Shorelines: A Scoping Review of Novel Restoration Strategies for Shoreline Protection - Carter S. Smith; Morgan E. Rudd; Rachel K. Gittman; Emily C. Melvin; Virginia S. Patterson; Julianna J. Renzi; Emory H. Wellman; Brian R. Silliman (Frontiers in Marine Science, 2020)

Photography as a tool for avian morphometric measurements - Heather M. Williams; Samantha B. Wilcox; Andrea J. Patterson (Journal of Ornithology, 2020)

NASA’s satellite laser ranging systems for the twenty-first century - J. F. McGarry; E. D. Hoffman; J. J. Degnan; J. W. Cheek; C. B. Clarke; I. F. Diegel; H. L. Donovan; J. E. Horvath; M. Marzouk; A. R. Nelson; D. S. Patterson; R. L. Ricklefs; et al. (Journal of Geodesy, 2019)

The time course of adaptations in thermoneutral maximal oxygen consumption following heat acclimation - Mark Waldron; O. Jeffries; J. Tallent; S. Patterson; V. Nevola (European Journal of Applied Physiology, 2019)
Purpose This study investigated the effects of a 10-day heat acclimation (HA) programme on the time course of changes in thermoneutral maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max ) during and up to 10 days post-HA. Methods Twenty-two male cyclists were assigned to a HA or control (Con) training group following baseline ramp tests of thermoneutral $$\dot{V}$$ V ˙ O 2max . Ten days of fixed-intensity (50% baseline $$\dot{V}$$ V ˙ O 2max ) indoor cycling was performed in either ~ 38.0 °C (HA) or ~ 20 °C (Con). $$\dot{V}$$ V ˙ O 2max was re-tested on HA days 5, 10 and post-HA days 1, 2, 3, 4, 5 and 10. Results $$\dot{V}$$ V ˙ O 2max initially declined across time in both groups during training ( P < 0.05), before increasing in the post-HA period in both groups ( P < 0.05). However, $$\dot{V}$$ V ˙ O 2max was higher than control by post-HA day 4 in the HA group ( P = 0.046). Conclusions The non-linear time course of $$\dot{V}$$ V ˙ O 2max adaptation suggests that post-testing should be performed 96-h post-training to identify the maximal change for most individuals. In preparation for training or testing, athletes can augment their aerobic power in thermoneutral environments by performing 10 days HA, but the full effects will manifest at varying stages of the post-HA period.

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Comparison of climate–growth responses of montane and piedmont longleaf pine (Pinus palustris Mill.) chronologies in North Carolina - Tyler J. Mitchell; Thomas W. Patterson; Paul A. Knapp (Trees, 2019)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Genotyping confirms significant cannibalism in northern Gulf of Mexico invasive red lionfish, Pterois volitans - Kristen A. Dahl; David S. Portnoy; J. Derek Hogan; John E. Johnson; John R. Gold; William F. Patterson (Biological Invasions, 2018)

Temporal and spatial differences in smolting among Oncorhynchus nerka populations throughout fresh and seawater migration - Marley C. Bassett; David A. Patterson; J. Mark Shrimpton (Journal of Fish Biology, 2018)
Physiological changes that occur in the spring are preparatory for salmonid smolts to successfully enter seawater, but variation is likely to exist within species with a wide geographic distribution. Whether differences in development of seawater tolerance exist among populations that differ in distance to the ocean, temporally during the spring, or as fish migrate downstream is not known. Juvenile sockeye salmon Oncorhynchus nerka from four regions in the Fraser River catchment, British Columbia, were intercepted to assess physiological differences among populations and at different times during migration to characterize the parr–smolt transformation. Pre‐migratory fish had low levels of gill Na + –K + ‐ATPase (NKA) activity. High gill NKA activities were observed at the start of migration for some populations, but smolts leaving the lake did not consistently have higher gill NKA activity than non‐migratory juvenile O. nerka sampled in their natal lakes. Gill NKA activity was highly variable at the start of migration with no relationship with distance from the ocean. Gill NKA activity changes with migration were also highly variable, but consistently smolts in the ocean had the highest enzyme activities. Internal and external factors may influence this variation, but the dynamic nature of smolting was not based on the region of origin, timing during migration or on the year of migration.

The effects of disproportional load contributions on quantifying vegetated filter strip sediment trapping efficiencies - Heather E. Gall; Daniel Schultz; Tamie L. Veith; Sarah C. Goslee; Alfonso Mejia; Ciaran J. Harman; Cibin Raj; Paul H. Patterson (Stochastic Environmental Research and Risk Assessment, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Factors affecting estimates of size at age and growth in grey triggerfish Balistes capriscus from the northern Gulf of Mexico - R. J. Allman; W. F. Patterson; C. L. Fioramonti; A. E. Pacicco (Journal of Fish Biology, 2018)
Growth zones in dorsal spines of grey triggerfish Balistes capriscus from the northern Gulf of Mexico were utilized to estimate growth and examine factors that may affect estimates of size at age. Age was estimated from dorsal‐spine sections of 4687 individuals sampled from U.S. waters during 2003–2013, including both fishery‐independent ( n = 1312) and fishery‐dependent ( n = 3375) samples. Ninety‐six per cent ( n = 4498) of these sections were deemed suitable for ageing; average per cent error between two independent readers was 10·8%. Fork length ( L F ) ranged from 65 to 697 mm and age estimates from 0 to 14 years. Both sex and sample source (fishery‐independent v . recreational) significantly affected estimated size at age for 2–6 year‐old fish. Data were pooled between sources to fit sex‐specific von Bertalanffy growth functions. Results for the female model were L ∞ = 387 mm L F , k = 0·52 year −1 and t 0 = 0·01 year, while for males L ∞ = 405 mm L F , k = 0·55 year −1 and t 0 = 0·02 year. These results were significantly different between sexes and indicate clear sexual dimorphism. Thus, growth should be modelled separately by sex when examining population parameters or conducting stock assessment modelling. The positive bias in estimates of size at age computed for recreational v . fishery‐independent samples also has clear implications for stock assessment as growth functions computed with fishery‐dependent samples would tend to overestimate stock productivity.

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Boundary Judgments in Water Governance: Diagnosing Internal and External Factors that Matter in a Complex World - Rob C. de Loë; James J. Patterson (Water Resources Management, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Natural variability and effects of cleaning and storage procedures on vertebral chemistry of the blacktip shark Carcharhinus limbatus - J. P. Lewis; W. F. Patterson; J. K. Carlson (Journal of Fish Biology, 2017)
Key methodological assumptions regarding the degree of natural variability and influence of sample handling and storage of elasmobranch vertebral chemistry were assessed using laser‐ablation inductively coupled plasma mass spectrometry. Vertebral chemistry of juvenile blacktip sharks Carcharhinus limbatus was examined to identify whether differences existed among different regions of the vertebral column, between thoracic vertebrae of individual fish or within individual vertebrae. Additionally, the effects of bleach exposure and storage in ethanol on vertebral chemistry were compared. No significant variation in vertebral chemistry was found among different regions of the vertebral column or between thoracic vertebrae, but significant differences among transect locations within individual vertebrae were observed. The variation at all three levels appears comparable with published data on sagittal otoliths of bilaterally symmetrical teleost fishes. The experimental assessment of potential treatment effects indicated vertebral chemistry was not significantly affected by bleach or exposure to ethanol. Taken together, these results support the idea that vertebrae taken from the same region of the vertebral column can be treated as equivalent and at least certain elements remain robust to exposure to bleach and ethanol.

Daily temperature experience and selection by adfluvial bull trout (Salvelinus confluentus) - L. F. G. Gutowsky; P. M. Harrison; E. G. Martins; A. Leake; D. A. Patterson; D. Z. Zhu; M. Power; S. J. Cooke (Environmental Biology of Fishes, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Individual isotopic specializations predict subsequent inter‐individual variation in movement in a freshwater fish - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; T. D. Ward; D. A. Patterson; S. J. Cooke; M. Power (Ecology, 2017)
Despite many similarities and intuitive links between individual dietary specialization and behavioral inter‐individual variation, these phenomena have been studied in isolation, and empirical data confirming relationships between these intraspecific variance sources are lacking. Here we use stable isotope analysis and acoustic telemetry to test the hypothesis that individual specialization in trophic (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) covary with inter‐individual variation in movement in a group of 34 free‐swimming burbot ( Lota lota ). By performing stable isotope analysis on tissues with differing isotopic turnover rates (anal fin and dorsal muscle), in 24 lethally sampled burbot, we demonstrate that individual specialization in trophic niche (δ 15 N) and littoral/pelagic prey reliance (δ 13 C) occurred within the population. By performing stable isotope analysis on anal fins of a group of telemetry tagged burbot, we were able to show that interactions between trophic niche and littoral/pelagic prey reliance, explained a significant proportion of the subsequent between‐individual variance in mean movement rates. These findings demonstrate an empirical connection between behavioral inter‐individual variation and dietary specialization, thus providing a substantial expansion of our understanding of the wider ecological consequences of these interesting phenomena.

Shrinking of Vann Island, Gulf of Mannar, SE coast of India: assessing the impacts - M. Jayaprakash; K. Sivakumar; S. Muthusamy; R. R. Krishnamurthy; J. K. Edward Patterson (Natural Hazards, 2016)

Putting the brakes on the brakes: negative emotion disrupts cognitive control network functioning and alters subsequent stopping ability - Tara K. Patterson; Agatha Lenartowicz; Elliot T. Berkman; Danni Ji; Russell A. Poldrack; Barbara J. Knowlton (Experimental Brain Research, 2016)

Effects of experimentally elevated egg cortisol on offspring traits in two species of wild Pacific salmon - Natalie M. Sopinka; Scott G. Hinch; Stephen J. Healy; Graham D. Raby; David A. Patterson (Environmental Biology of Fishes, 2016)

Burbot and large hydropower in North America: benefits, threats and research needs for mitigation - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Fisheries Management and Ecology, 2016)
In North America, burbot Lota lota (L.), interactions with hydropower are common, southern burbot populations are endangered and hydropower has been implicated in the decline. Thus, the objectives of this review were to identify threats and benefits of hydropower to riverine and reservoir dwelling burbot, assess overall impacts and identify key research needs for mitigation. Review findings suggest that while winter hydropower discharge regimes threaten riverine burbot spawning, burbot often successfully exploit reservoir environments. Further, while turbine entrainment has been hypothesised as a factor in the decline of burbot populations, low adult vulnerability to passage and a high resilience to juvenile removals likely mean risk to populations is low. Identified research needs include better definitions of flow and temperature requirements for riverine burbot and a quantification of the potential for reservoirs to act as source populations for downstream impacted zones. This review highlights the Pacific watershed focus of existing work and calls for status assessments and ecological research of burbot in North American Arctic and Atlantic watersheds where large hydropower and burbot interactions are common yet rarely studied.

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Temporal plasticity in thermal‐habitat selection of burbot Lota lota a diel‐migrating winter‐specialist - P. M. Harrison; L. F. G. Gutowsky; E. G. Martins; D. A. Patterson; S. J. Cooke; M. Power (Journal of Fish Biology, 2016)
In this study, animal‐borne telemetry with temperature sensors was coupled with extensive habitat temperature monitoring in a dimictic reservoir, to test the following hypotheses: behavioural thermoregulation occurs throughout the year and temperature selection varies on a diel and seasonal basis, in a winter‐specialist diel‐migrating fish. Burbot Lota lota demonstrated nightly behavioural thermoregulation throughout the year, with a large seasonal shift between selection for very cold temperatures ( L. lota avoided habitats warmer than optimal for reproduction and feeding during the spawning and non‐reproductive periods, respectively, active selection was limited to selection for 4–6° C habitat during the prespawning period. Although behavioural thermoregulation explained the night‐time migration, behavioural thermoregulation only partially explained daytime behaviour, indicating that diel migration is best explained by a combination of factors. Thus, thermal‐habitat selection was a good predictor of night‐time habitat occupancy in a diel‐migrating species. Together, these results show that thermal‐habitat selection by fishes may be important throughout the year and a more seasonally plastic behaviour than previously recognized.

Combined evidence indicates that Perna indica Kuriakose and Nair 1976 is Perna perna (Linnaeus, 1758) from the Oman region introduced into southern India more than 100 years ago - Jonathan P. A. Gardner; Jamila Patterson; Sanil George; J. K. Patterson Edward (Biological Invasions, 2016)

Changes of Sorghum bicolor landrace diversity and farmers’ selection criteria over space and time, Ethiopia - Awegechew Teshome; Daniel Patterson; Zemede Asfaw; Sarah Dalle; J. Kenneth Torrance (Genetic Resources and Crop Evolution, 2016)

First record of coralline lethal orange disease (CLOD) in the Indian Ocean - G. S. Aeby; K. Diraviya Raj; G. Mathews; M. Selva Bharath; J. K. Patterson Edward (Coral Reefs, 2015)

Benzotriazoles in the Aquatic Environment: a Review of Their Occurrence, Toxicity, Degradation and Analysis - M. D. Alotaibi; A. J. McKinley; B. M. Patterson; A. Y. Reeder (Water, Air, & Soil Pollution, 2015)

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Enabling and Enacting ‘Practical Action’ in Catchments: Responding to the ‘Wicked Problem’ of Nonpoint Source Pollution in Coastal Subtropical Australia - James J. Patterson; Carl Smith; Jennifer Bellamy (Environmental Management, 2015)

Determining trends and environmental drivers from long-term marine mammal and seabird data: examples from Southern Australia - Lynda E. Chambers; Toby Patterson; Alistair J. Hobday; John P. Y. Arnould; Geoffrey N. Tuck; Chris Wilcox; Peter Dann (Regional Environmental Change, 2015)

Thermal regime, predation danger and the early marine exit of sockeye salmon Oncorhynchus nerka - P. J. Katinic; D. A. Patterson; R. C. Ydenberg (Journal of Fish Biology, 2015)
Marine exit timing of sockeye salmon Oncorhynchus nerka populations on the Haida Gwaii Archipelago, British Columbia, Canada, is described, with specific focus on Copper Creek. Marine exit in Copper Creek occurs > 130 days prior to spawning, one of the longest adult freshwater residence periods recorded for any O. nerka population. Copper Creek presents an easy upstream migration, with mild water temperatures (7 to 14° C), short distance (13·1 km) and low elevation gain (41 m) to the lake where fish hold prior to spawning. An energetic model estimates that O.nerka streams in Haida Gwaii has ever exceeded the presumed temperature threshold (19° C) for early marine exit. Although it is not impossible that the thermal tolerance of Copper Creek O.nerka is very low, the data presented here appear inconsistent with thermal avoidance as an explanation for the early marine exit timing in Copper Creek and in three other populations on the archipelago with early marine exit.

Life history of harbor porpoises ( Phocoena phocoena ) in Scottish ( UK ) waters - Jennifer A. Learmonth; Sinead Murphy; Patricia L. Luque; Robert J. Reid; I. Anthony P. Patterson; Andrew Brownlow; Harry M. Ross; Jason P. Barley; M. Begoña Santos; Graham J. Pierce (Marine Mammal Science, 2014)
Life history parameters were determined for stranded and bycaught harbor porpoises ( Phocoena phocoena ) from Scottish ( UK ) waters (1992–2005). Fetal growth rate was 84.4 mm/mo and mean size at birth was 76.4 cm (range 65–88 cm). Males and females had a similar range of body lengths (65–170 cm and 66–173 cm, respectively), although asymptotic lengths were higher in females than males (approximately 158 cm and 147 cm, respectively). Nonpregnant females were significantly lighter, in relation to their length than males. Maximum estimated age was 20 yr for both sexes. Age at sexual maturity ( ASM ) was estimated as 4.35 yr in females and 5.00 yr in males. Conception occurred mainly in July and August although reproductively active males were recorded during April to July. Gestation lasted 10–11 mo, with calving mainly between May and July. Lactating females were recorded during June to November, while small calves with solid food in their stomachs were found mainly during February to May. Estimated pregnancy rate (0.34–0.40) is lower than recorded elsewhere, but is likely underestimated due to the prevalence of mature females of poor health status in the sample. Nevertheless, cetacean strandings can be an essential source of data on demographic parameters.

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Hepatic Transcriptome Profiles Differ Among Maturing Beef Heifers Supplemented with Inorganic, Organic, or Mixed (50 % Inorganic:50 % Organic) Forms of Dietary Selenium - James C. Matthews; Zhi Zhang; Jennifer D. Patterson; Phillip J. Bridges; Arnold J. Stromberg; J. A. Boling (Biological Trace Element Research, 2014)

Middle to late Holocene chironomid-inferred July temperatures for the central Northwest Territories, Canada - Lindsay M. Upiter; Jesse C. Vermaire; R. Timothy Patterson; Carley A. Crann; Jennifer M. Galloway; Andrew L. Macumber; Lisa A. Neville; Graeme T. Swindles; Hendrik Falck; Helen M. Roe; Michael F. J. Pisaric (Journal of Paleolimnology, 2014)

Mother knows best, even when stressed? Effects of maternal exposure to a stressor on offspring performance at different life stages in a wild semelparous fish - N. M. Sopinka; S. G. Hinch; C. T. Middleton; J. A. Hills; D. A. Patterson (Oecologia, 2014)

Discussions and decisions of the 2012–2014 International Committee on Taxonomy of Viruses (ICTV) Filoviridae Study Group, January 2012–June 2013 - Alexander A. Bukreyev; Kartik Chandran; Olga Dolnik; John M. Dye; Hideki Ebihara; Eric M. Leroy; Elke Mühlberger; Sergey V. Netesov; Jean L. Patterson; Janusz T. Paweska; Erica Ollmann Saphire; Sophie J. Smither; et al. (Archives of Virology, 2014)

A protected area influences genotype‐specific survival and the structure of a Canis hybrid zone - John F. Benson; Brent R. Patterson; Peter J. Mahoney (Ecology, 2014)
It is widely recognized that protected areas can strongly influence ecological systems and that hybridization is an important conservation issue. However, previous studies have not explicitly considered the influence of protected areas on hybridization dynamics. Eastern wolves are a species of special concern and their distribution is largely restricted to a protected population in Algonquin Provincial Park (APP), Ontario, Canada, where they are the numerically dominant canid. We studied intrinsic and extrinsic factors influencing survival and cause‐specific mortality of hybrid and parental canids in the three‐species hybrid zone between eastern wolves, eastern coyotes, and gray wolves in and adjacent to APP. Mortality risk for eastern wolves in areas adjacent to APP was significantly higher than for other sympatric Canis types outside of APP, and for eastern wolves and other canids within APP. Outside of APP, the annual mortality rate of all canids by harvest (24%) was higher than for other causes of death (4–7%). Furthermore, eastern wolves (hazard ratio = 3.5) and nonresidents (transients and dispersing animals, hazard ratio = 2.7) were more likely to die from harvest relative to other Canis types and residents, respectively. Thus, eastern wolves dispersing from APP were especially vulnerable to harvest mortality. For residents, eastern wolf survival was more negatively influenced by increased road density than for other Canis types, further highlighting the sensitivity of eastern wolves to human disturbance. A cycle of dispersal from APP followed by high rates of mortality and hybridization appears to maintain eastern wolves at low density adjacent to APP, limiting the potential for expansion beyond the protected area. However, high survival and numerical dominance of eastern wolves within APP suggest that protected areas can allow rare hybridizing species to persist even if their demographic performance is compromised and barriers to hybridization are largely absent in the adjacent matrix.

Incorporating Climate and Ocean Change into Extinction Risk Assessments for 82 Coral Species - RUSSELL E. BRAINARD; MARISKA WEIJERMAN; C. MARK EAKIN; PAUL MCELHANY; MARGARET W. MILLER; MATT PATTERSON; GREGORY A. PINIAK; MATTHEW J. DUNLAP; CHARLES BIRKELAND (Conservation Biology, 2013)
Many marine invertebrate species facing potential extinction have uncertain taxonomies and poorly known demographic and ecological traits. Uncertainties are compounded when potential extinction drivers are climate and ocean changes whose effects on even widespread and abundant species are only partially understood. The U.S. Endangered Species Act mandates conservation management decisions founded on the extinction risk to species based on the best available science at the time of consideration—requiring prompt action rather than awaiting better information. We developed an expert‐opinion threat‐based approach that entails a structured voting system to assess extinction risk from climate and ocean changes and other threats to 82 coral species for which population status and threat response information was limited. Such methods are urgently needed because constrained budgets and manpower will continue to hinder the availability of desired data for many potentially vulnerable marine species. Significant species‐specific information gaps and uncertainties precluded quantitative assessments of habitat loss or population declines and necessitated increased reliance on demographic characteristics and threat vulnerabilities at genus or family levels. Adapting some methods (e.g., a structured voting system) used during other assessments and developing some new approaches (e.g., integrated assessment of threats and demographic characteristics), we rated the importance of threats contributing to coral extinction risk and assessed those threats against population status and trend information to evaluate each species’ extinction risk over the 21st century. This qualitative assessment resulted in a ranking with an uncertainty range for each species according to their estimated likelihood of extinction. We offer guidance on approaches for future biological extinction risk assessments, especially in cases of data‐limited species likely to be affected by global‐scale threats. Incorporación del Cambio Climático y Oceánico en Estudios de Riesgo de Extinción para 82 Especies de Coral

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Preface - Tucker A. Patterson; W. Gibson Wood; Russell J. Andrews; William Slikker (Molecular Neurobiology, 2013)

Genetic perspectives on “Lion Conservation Units” in Eastern and Southern Africa - J. M. Dubach; M. B. Briggs; P. A. White; B. A. Ament; B. D. Patterson (Conservation Genetics, 2013)

Stable isotopes identify an ontogenetic niche expansion in Antarctic krill (Euphausia superba) from the South Shetland Islands, Antarctica - Michael J. Polito; Christian S. Reiss; Wayne Z. Trivelpiece; William P. Patterson; Steven D. Emslie (Marine Biology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Conserving large carnivores: dollars and fence - C. Packer; A. Loveridge; S. Canney; T. Caro; S.T. Garnett; M. Pfeifer; K.K. Zander; A. Swanson; D. MacNulty; G. Balme; H. Bauer; C.M. Begg; et al. (Ecology Letters, 2013)
Conservationists often advocate for landscape approaches to wildlife management while others argue for physical separation between protected species and human communities, but direct empirical comparisons of these alternatives are scarce. We relate African lion population densities and population trends to contrasting management practices across 42 sites in 11 countries. Lion populations in fenced reserves are significantly closer to their estimated carrying capacities than unfenced populations. Whereas fenced reserves can maintain lions at 80% of their potential densities on annual management budgets of $500 km −2 , unfenced populations require budgets in excess of $2000 km −2 to attain half their potential densities. Lions in fenced reserves are primarily limited by density dependence, but lions in unfenced reserves are highly sensitive to human population densities in surrounding communities, and unfenced populations are frequently subjected to density‐independent factors. Nearly half the unfenced lion populations may decline to near extinction over the next 20–40 years.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Effects of body mass and water temperature on routine metabolism of American paddlefish Polyodon spathula - J. T. Patterson; S. D. Mims; R. A. Wright (Journal of Fish Biology, 2013)
This study quantified the effects of temperature and fish mass on routine metabolism of the American paddlefish Polyodon spathula . Thermal sensitivity, as measured by Q 10 value, was low in P. spathula . Mean Q 10 was 1·78 while poikilotherms are generally expected to have Q 10 values in the 2·00–2·50 range. Mass‐specific metabolism did not decrease with increased fish size to the extent that this phenomenon is observed in teleosts, as evidenced by a mass exponent ( β ) value of 0·92 for P. spathula compared with 0·79 in a review of teleost species. Other Acipenseriformes have exhibited relatively high β values for mass‐specific respiration. Overall P. spathula metabolism appears to be more dependent on body mass and less dependent on temperature than for many other fishes. An equation utilizing temperature and fish mass to estimate gross respiration for P. spathula was derived and this equation was applied to respiratory data from other Acipenseriformes to assess inter‐species variation. Polyodon spathula respiration rates across water temperature and fish mass appear most similar to those of Atlantic sturgeon Acipenser naccarii and white sturgeon Acipenser transmontanus .

The physiological consequences of catch‐and‐release angling: perspectives on experimental design, interpretation, extrapolation and relevance to stakeholders - S. J. Cooke; M. R. Donaldson; C. M. O'connor; G. D. Raby; R. Arlinghaus; A. J. Danylchuk; K. C. Hanson; S. G. Hinch; T. D. Clark; D. A. Patterson; C. D. Suski (Fisheries Management and Ecology, 2013)
Over the past 20 years, there has been a dramatic increase in the use of physiological tools and experimental approaches for the study of the biological consequences of catch‐and‐release angling practices for fishes. Beyond simply documenting problems, physiological data are also being used to test and refine different strategies for handling fish such that stress is minimised and survival probability maximised, and in some cases, even for assessing and facilitating recovery post‐release. The inherent sensitivity of physiological processes means that nearly every study conducted has found some level of – unavoidable – physiological disturbance arising from recreational capture and subsequent release. An underlying tenet of catch‐and‐release studies that incorporate physiological tools is that a link exists between physiological status and fitness. In reality, finding such relationships has been elusive, with further extensions of individual‐level impacts to fish populations even more dubious. A focus of this article is to describe some of the challenges related to experimental design and interpretation that arise when using physiological tools for the study of the biological consequences of catch‐and‐release angling. Means of overcoming these challenges and the extrapolation of physiological data from individuals to the population level are discussed. The argument is presented that even if it is difficult to demonstrate strong links to mortality or other fitness measures, let alone population‐level impacts of catch‐and‐release, there remains merit in using physiological tools as objective indicators of fish welfare, which is an increasing concern in recreational fisheries. The overarching objective of this paper is to provide a balanced critique of the use of physiological approaches in catch‐and‐release science and of their role in providing meaningful information for anglers and managers.

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Climate effects on growth, phenology, and survival of sockeye salmon (Oncorhynchus nerka): a synthesis of the current state of knowledge and future research directions - Eduardo G. Martins; Scott G. Hinch; Steven J. Cooke; David A. Patterson (Reviews in Fish Biology and Fisheries, 2012)

Spatial genetic and morphologic structure of wolves and coyotes in relation to environmental heterogeneity in a C anis hybrid zone - John F. Benson; Brent R. Patterson; Tyler J. Wheeldon (Molecular Ecology, 2012)
Eastern wolves have hybridized extensively with coyotes and gray wolves and are listed as a ‘species of special concern’ in C anada. However, a distinct population of eastern wolves has been identified in A lgonquin P rovincial P ark ( APP ) in O ntario. Previous studies of the diverse C anis hybrid zone adjacent to APP have not linked genetic analysis with field data to investigate genotype‐specific morphology or determine how resident animals of different ancestry are distributed across the landscape in relation to heterogeneous environmental conditions. Accordingly, we studied resident wolves and coyotes in and adjacent to APP to identify distinct C anis types, clarify the extent of the APP eastern wolf population beyond the park boundaries and investigate fine‐scale spatial genetic structure and landscape–genotype associations in the hybrid zone. We documented three genetically distinct C anis types within the APP region that also differed morphologically, corresponding to putative gray wolves, eastern wolves and coyotes. We also documented a substantial number of hybrid individuals (36%) that were admixed between 2 or 3 of the C anis types. Breeding eastern wolves were less common outside of APP , but occurred in some unprotected areas where they were sympatric with a diverse combination of coyotes, gray wolves and hybrids. We found significant spatial genetic structure and identified a steep cline extending west from APP where the dominant genotype shifted abruptly from eastern wolves to coyotes and hybrids. The genotypic pattern to the south and northwest was a more complex mosaic of alternating genotypes. We modelled genetic ancestry in response to prey availability and human disturbance and found that individuals with greater wolf ancestry occupied areas of higher moose density and fewer roads. Our results clarify the structure of the C anis hybrid zone adjacent to APP and provide unique insight into environmental conditions influencing hybridization dynamics between wolves and coyotes.

Modeling the Yew Tree Tubulin and a Comparison of its Interaction with Paclitaxel to Human Tubulin - Jack A. Tuszynski; Travis J. A. Craddock; Jonathan Y. Mane; Khaled Barakat; Chih-Yuan Tseng; Melissa Gajewski; Philip Winter; Laleh Alisaraie; Jordan Patterson; Eric Carpenter; Weiwei Wang; Michael K. Deyholos; et al. (Pharmaceutical Research, 2012)

Measurement of Bremsstrahlung radiation for in vivo monitoring of 14C tracer distribution between fruit and roots of kiwifruit (Actinidia arguta) cuttings - Marykate Z. Black; Peter E. H. Minchin; Nick Gould; Kevin J. Patterson; Michael J. Clearwater (Planta, 2012)

Exertional thermal strain, protective clothing and auxiliary cooling in dry heat: evidence for physiological but not cognitive impairment - Joanne N. Caldwell; Mark J. Patterson; Nigel A. S. Taylor (European Journal of Applied Physiology, 2012)

Vertebrate metacommunity structure along an extensive elevational gradient in the tropics: a comparison of bats, rodents and birds - Steven J. Presley; Laura M. Cisneros; Bruce D. Patterson; Michael R. Willig (Global Ecology and Biogeography, 2012)
Aim We evaluated the structure of metacommunities for each of three vertebrate orders (Chiroptera, Rodentia and Passeriformes) along an extensive elevational gradient. Using elevation as a proxy for variation in abiotic characteristics and the known elevational distributions of habitat types, we assessed the extent to which variation in those factors may structure each metacommunity based on taxon‐specific characteristics. Location Manu Biosphere Reserve in the Peruvian Andes. Methods Metacommunity structure is an emergent property of a set of species distributions across geographic or environmental gradients. We analysed elements of metacommunity structure (coherence, range turnover and range boundary clumping) to determine the best‐fit structure for each metacommunity along an elevational gradient comprising 13 250‐m elevational intervals and 58 species of rodent, 92 species of bat or 586 species of passerine. Results For each taxon, the environmental gradient along which the metacommunity was structured was highly correlated with elevation. Clementsian structure (i.e. groups of species replacing other such groups along the gradient) characterized rodents, with a group of species that was characteristic of rain forests and a group of species that was characteristic of higher elevation habitats (i.e. above 1500 m). Distributions of bats were strongly nested, with more montane communities comprising subsets of species at lower elevations. The structure of the passerine metacommunity was complex and most consistent with a quasi‐Clementsian structure. Main conclusions Each metacommunity exhibited a different structure along the same elevational gradient, and each structure can be accounted for by taxon‐specific responses to local environmental factors that vary predictably with elevation. The structures of rodent and bird metacommunities suggest species sorting associated with habitat specializations, whereas structure of the bat metacommunity is probably moulded by a combination of species‐specific tolerances to increasingly cold, low‐productivity environs of higher elevations and the diversity and abundance of food resources associated with particular habitat types.

Observations on saliva osmolality during progressive dehydration and partial rehydration - Nigel A. S. Taylor; Anne M. J. van den Heuvel; Pete Kerry; Sheena McGhee; Gregory E. Peoples; Marc A. Brown; Mark J. Patterson (European Journal of Applied Physiology, 2012)

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka - S. G. Hinch; S. J. Cooke; A. P. Farrell; K. M. Miller; M. Lapointe; D. A. Patterson (Journal of Fish Biology, 2012)
Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3–6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few days in some years (termed early migration), with dramatic consequences that have necessitated risk‐averse management strategies. Early migrating fish consistently suffer extremely high mortality (exceeding 90% in some years) during freshwater migration and on spawning grounds prior to spawning. This synthesis examines multidisciplinary, collaborative research aimed at understanding what triggers early migration, why it results in high mortality, and how fisheries managers can utilize these scientific results. Tissue analyses from thousands of O. nerka captured along their migration trajectory from ocean to spawning grounds, including hundreds that were tracked with biotelemetry, have revealed that early migrants are more reproductively advanced and ill‐prepared for osmoregulatory transition upon their entry into fresh water. Gene array profiles indicate that many early migrants are also immunocompromised and stressed, carrying a genomic profile consistent with a viral infection. The causes of these physiological changes are still under investigation. Early migration brings O. nerka into the river when it is 3–6° C warmer than historical norms, which for some late‐run populations approaches or exceeds their critical maxima leading to the collapse of metabolic and cardiac scope, and mortality. As peak spawning dates have not changed, the surviving early migrants tend to mill in warm lakes near to spawning areas. These results in the accumulation of many more thermal units and longer exposures to freshwater diseases and parasites compared to fish that delay freshwater entry by milling in the cool ocean environment. Experiments have confirmed that thermally driven processes are a primary cause of mortality for early‐entry migrants. The Fraser River late‐run O. nerka early migration phenomenon illustrates the complex links that exist between salmonid physiology, behaviour and environment and the pivotal role that water temperature can have on population‐specific migration survival.

Quantitative methods for analysing cumulative effects on fish migration success: a review - J. E. Johnson; D. A. Patterson; E. G. Martins; S. J. Cooke; S. G. Hinch (Journal of Fish Biology, 2012)
It is often recognized, but seldom addressed, that a quantitative assessment of the cumulative effects, both additive and non‐additive, of multiple stressors on fish survival would provide a more realistic representation of the factors that influence fish migration. This review presents a compilation of analytical methods applied to a well‐studied fish migration, a more general review of quantitative multivariable methods, and a synthesis on how to apply new analytical techniques in fish migration studies. A compilation of adult migration papers from Fraser River sockeye salmon Oncorhynchus nerka revealed a limited number of multivariable methods being applied and the sub‐optimal reliance on univariable methods for multivariable problems. The literature review of fisheries science, general biology and medicine identified a large number of alternative methods for dealing with cumulative effects, with a limited number of techniques being used in fish migration studies. An evaluation of the different methods revealed that certain classes of multivariable analyses will probably prove useful in future assessments of cumulative effects on fish migration. This overview and evaluation of quantitative methods gathered from the disparate fields should serve as a primer for anyone seeking to quantify cumulative effects on fish migration survival.

Effectiveness of short-term heat acclimation for highly trained athletes - Andrew T. Garrett; Rob Creasy; Nancy J. Rehrer; Mark J. Patterson; James D. Cotter (European Journal of Applied Physiology, 2012)

The complimentary role of genetic and ecological data in understanding population structure: a case study using moose (Alces alces) - L. A. Finnegan; P. J. Wilson; G. N. Price; S. J. Lowe; B. R. Patterson; M.-J. Fortin; D. L. Murray (European Journal of Wildlife Research, 2012)

Coastal community resilience: analysis of resilient elements in 3 districts of Tamil Nadu State, India - Sushma Guleria; J. K. Patterson Edward (Journal of Coastal Conservation, 2012)

Canine epilepsy genetics - Kari J. Ekenstedt; Edward E. Patterson; James R. Mickelson (Mammalian Genome, 2012)

Parental identity influences progeny responses to incubation thermal stress in sockeye salmon Onchorhynchus nerka - J. M. Burt; S. G. Hinch; D. A. Patterson (Journal of Fish Biology, 2012)
The influence of individual parentage on progeny responses to early developmental temperature stress was examined in a cross‐fertilization experiment using sockeye salmon Oncorhynchus nerka . Differences in survival, hatch timing and size were examined among five paternally linked and five maternally linked offspring families (Weaver Creek population, British Columbia, Canada) incubated at 12, 14 and 16° C from just after fertilization to hatch. Mean embryonic survival was significantly lower at 14 and 16° C; however, offspring families had substantially different survival responses across the thermal gradient (crossing reaction norms). Within temperature treatments, substantial variation in embryonic survival, alevin mass, time‐to‐hatch and hatch duration were attributable to family identity; however, most traits were governed by significant temperature–family interactions. For embryonic survival, large differences between families at 16° C were due to both female and male spawner influence, whereas inter‐family differences were obscured at 14° C (high intra‐family variation), and minimal at 12° C (only maternal influence detected). Despite post‐hatch rearing under a common cool thermal regime, persistent effects of both temperature and parentage were detected in alevin and 3 week‐old fry. Collectively, these findings highlight the crucial role that parental influences on offspring may have in shaping future selection within salmonid populations exposed to elevated thermal regimes. An increased understanding of parental and temperature influences and their persistence in early development will be essential to developing a more comprehensive view of population spawning success and determining the adaptive capacity of O. nerka populations in the face of environmental change.

Physiological and molecular endocrine changes in maturing wild sockeye salmon, Oncorhynchus nerka, during ocean and river migration - A.-M. Flores; J. M. Shrimpton; D. A. Patterson; J. A. Hills; S. J. Cooke; T. Yada; S. Moriyama; S. G. Hinch; A. P. Farrell (Journal of Comparative Physiology B, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

The efficacy of field techniques for obtaining and storing blood samples from fishes - T. D. Clark; M. R. Donaldson; S. M. Drenner; S. G. Hinch; D. A. Patterson; J. Hills; V. Ives; J. J. Carter; S. J. Cooke; A. P. Farrell (Journal of Fish Biology, 2011)
Prompted by the dramatic increase in the use of blood analyses in fisheries research and monitoring, this study investigated the efficacy of common field techniques for sampling and storing blood from fishes. Three questions were addressed: (1) Do blood samples taken via rapid caudal puncture (the ‘grab‐and‐stab’ technique) yield similar results for live v. sacrificed groups of fishes? (2) Do rapidly obtained caudal blood samples accurately represent blood properties of fishes prior to capture? (3) Does storage of whole blood in an ice slurry for a working day (8·5 h) modify the properties of the plasma? It was shown that haematocrit, plasma ions, metabolites, stress hormones and sex hormones of caudal blood samples were statistically similar when taken from live v. recently sacrificed groups of adult coho salmon Oncorhynchus kisutch . Moreover, this study confirmed by using paired blood samples from cannulated O. kisutch that blood acquired through the caudal puncture technique (mean ± s.e . 142 ± 26 s after capture) was representative of fish prior to capture. Long‐term (8·5 h) cold storage of sockeye salmon Oncorhynchus nerka whole blood caused significant decreases in plasma potassium and chloride, and a significant increase in plasma glucose. Previous research has suggested that these changes largely result from net movements of ions and molecules between the plasma and erythrocytes, movements that can occur within minutes of storage. Thus, blood samples from fishes should be centrifuged as quickly as practicable in the field for separation of plasma and erythrocytes to prevent potentially misleading data.

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

The importance of parentage in assessing temperature effects on fish early life history: a review of the experimental literature - J. M. Burt; S. G. Hinch; D. A. Patterson (Reviews in Fish Biology and Fisheries, 2011)

The After Breast Cancer Pooling Project: rationale, methodology, and breast cancer survivor characteristics - Sarah J. Nechuta; Bette J. Caan; Wendy Y. Chen; Shirley W. Flatt; Wei Lu; Ruth E. Patterson; Elizabeth M. Poole; Marilyn L. Kwan; Zhi Chen; Erin Weltzien; John P. Pierce; Xiao Ou Shu (Cancer Causes & Control, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

High Performance Thin Layer Chromatography (HPTLC) profile of an insecticidal compound of Trochus radiatus and assessment of mucus-associated bacterial extracts - Mary Elizabeth K. Gnanambal; K. C. Ramya Devi; P. Hareesh Chandra; Edward J. K. Patterson (Phytoparasitica, 2011)

Selenium in surface and irrigation water in the Kendrick irrigation district, Wyoming - Michelle M. Patterson; Ginger B. Paige; Katta J. Reddy (Environmental Monitoring and Assessment, 2010)

Efficacy of caspofungin as salvage therapy for invasive aspergillosis compared to standard therapy in a historical cohort - J. W. Hiemenz; I. I. Raad; J. A. Maertens; R. Y. Hachem; A. J. Saah; C. A. Sable; J. A. Chodakewitz; M. E. Severino; P. Saddier; R. S. Berman; D. M. Ryan; M. J. DiNubile; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Infection of gill and kidney of Fraser River sockeye salmon, Oncorhynchus nerka (Walbaum), by Parvicapsula minibicornis and its effect on host physiology - M J Bradford; J Lovy; D A Patterson (Journal of Fish Diseases, 2010)
Adult sockeye salmon, Oncorhynchus nerka (Walbaum), migrating upstream in the Fraser River, British Columbia, are exposed to the myxozoan parasite Parvicapsula minibicornis when they enter the river from the ocean. Infections are initially localized in the kidney but have recently been associated with branchitis in one population. Adult fish from five locations in the watershed were sampled to determine whether branchitis was widespread. P. minibicornis infections in kidney glomeruli were prevalent in all samples except for a sample of fish that had just entered the Fraser River from the ocean. For fish captured in spawning streams, parasites were observed in the renal tubules and gill, and branchitis was observed in 70% of fish. Plasma osmolality was negatively correlated with the number of parasites in the kidney tubules, which we hypothesize to be caused by the breach of glomerular membranes as the parasite leaves the fish. Plasma lactate values increased with increasing levels of pathology in gills. These findings support the hypothesis that P. minibicornis impacts the physiology of migrating fish, which may in turn affect the likelihood that adults will be able to migrate and spawn successfully.

A new high-latitude record for the macaroni penguin (Eudyptes chrysolophus) at Avian Island, Antarctica - K. B. Gorman; E. S. Erdmann; B. C. Pickering; P. J. Horne; J. R. Blum; H. M. Lucas; D. L. Patterson-Fraser; W. R. Fraser (Polar Biology, 2010)

Human sewage identified as likely source of white pox disease of the threatened Caribbean elkhorn coral, Acropora palmata - Kathryn Patterson Sutherland; James W. Porter; Jeffrey W. Turner; Brian J. Thomas; Erin E. Looney; Trevor P. Luna; Meredith K. Meyers; J. Carrie Futch; Erin K. Lipp (Environmental Microbiology, 2010)
Summary Caribbean elkhorn coral, Acropora palmata , has been decimated in recent years, resulting in the listing of this species as threatened under the United States Endangered Species Act. A major contributing factor in the decline of this iconic species is white pox disease. In 2002, we identified the faecal enterobacterium, Serratia marcescens , as an etiological agent for white pox. During outbreaks in 2003 a unique strain of S. marcescens was identified in both human sewage and white pox lesions. This strain (PDR60) was also identified from corallivorious snails ( Coralliophila abbreviata ), reef water, and two non‐acroporid coral species, Siderastrea siderea and Solenastrea bournoni . Identification of PDR60 in sewage, diseased Acropora palmata and other reef invertebrates within a discrete time frame suggests a causal link between white pox and sewage contamination on reefs and supports the conclusion that humans are a likely source of this disease.

Larval supply is a good predictor of recruitment in endemic but not non-endemic fish populations at a high latitude coral reef - A. J. Crean; S. E. Swearer; H. M. Patterson (Coral Reefs, 2010)

Interaction between cyanobacterial copper chaperone Atx1 and zinc homeostasis - Samantha J. Dainty; Carl J. Patterson; Kevin J. Waldron; Nigel J. Robinson (JBIC Journal of Biological Inorganic Chemistry, 2010)

Testing the synergistic effects of GnRH and testosterone on the reproductive physiology of pre‐adult pink salmon Oncorhynchus gorbuscha - G. T. Crossin; S. G. Hinch; S. J. Cooke; D. A. Patterson; A. G. Lotto; G. Van Der Kraak; Y. Zohar; U. Klenke; A. P. Farrell (Journal of Fish Biology, 2010)
To test the hypothesis that the hypothalmic gonadotropin‐releasing hormone (GnRH) and testosterone (T) co‐treatment stimulates both the hypothalmo–pituitary–gonadal (HPG) and hypothalmo–pituitary–interrenal axes, the reproductive and osmoregulatory responses of pre‐adult pink salmon Oncorhynchus gorbuscha were compared after GnRH and T administration either alone or in combination. Relative to controls, neither GnRH nor T treatment resulted in significantly greater ovarian or testicular growth, but co‐treatment significantly increased ovarian growth after 5 months. Interestingly, the stimulation was undetectable after 3 months. However, once daily photoperiod began shortening after the summer solstice, c. 2 months before the natural spawning date, GnRH+T‐treated females were stimulated to produce larger ovaries. Final fish body length and the size of individual eggs did not differ among treatment groups. GnRH+T eggs, however, showed signs of advanced vitellogenesis relative to GnRH‐treated and control eggs, whereas T‐treated eggs became atretic. Testis size increased significantly from initial values and most males were spermiating, but this growth and development were independent of hormone treatments. Final plasma ion, metabolite and cortisol concentrations did not differ among treatment groups. It is concluded that GnRH+T co‐treatment was effective in stimulating female but not male maturation. GnRH and T treatment, however, presumably had little effect on the hypothalmo–pituitary–interrenal axis as observed by ionoregulatory status.

Using GPS data to evaluate the accuracy of state–space methods for correction of Argos satellite telemetry error - Toby A. Patterson; Bernie J. McConnell; Mike A. Fedak; Mark V. Bravington; Mark A. Hindell (Ecology, 2010)
Recent studies have applied state–space models to satellite telemetry data in order to remove noise from raw location estimates and infer the true tracks of animals. However, while the resulting tracks may appear plausible, it is difficult to determine the accuracy of the estimated positions, especially for position estimates interpolated to times between satellite locations. In this study, we use data from two gray seals ( Halichoerus grypus ) carrying tags that transmitted Fastloc GPS positions via Argos satellites. This combination of Service Argos data and highly accurate GPS data allowed examination of the accuracy of state–space position estimates and their uncertainty derived from satellite telemetry data. After applying a speed filter to remove aberrant satellite telemetry locations, we fit a continuous‐time Kalman filter to estimate the parameters of a random walk, used Kalman smoothing to infer positions at the times of the GPS measurements, and then compared the filtered telemetry estimates with the actual GPS measurements. We investigated the effect of varying maximum speed thresholds in the speed‐filtering algorithm on the root mean‐square error (RMSE) estimates and used minimum RMSE as a criterion to guide the final choice of speed threshold. The optimal speed thresholds differed between the two animals (1.1 m/s and 2.5 m/s) and retained 50% and 65% of the data for each seal. However, using a speed filter of 1.1 m/s resulted in very similar RMSE for both animals. For the two seals, the RMSE of the Kalman‐filtered estimates of location were 5.9 and 12.76 km, respectively, and 75% of the modeled positions had errors less than 6.25 km and 11.7 km for each seal. Confidence interval coverage was close to correct at typical levels (80–95%), although it tended to be overly generous at smaller sizes. The reliability of uncertainty estimates was also affected by the chosen speed threshold. The combination of speed and Kalman filtering allows for effective calculation of location and also indicates the limits of accuracy when correcting service Argos locations and linking satellite telemetry data to spatial covariate and habitat data.

Erratum to: Induction and decay of short-term heat acclimation - Andrew T. Garrett; Niels G. Goosens; Nancy J. Rehrer; Mark J. Patterson; James D. Cotter (European Journal of Applied Physiology, 2009)

Induction and decay of short-term heat acclimation - Andrew T. Garrett; Niels G. Goosens; Nancy G. Rehrer; Mark J. Patterson; James D. Cotter (European Journal of Applied Physiology, 2009)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

The influence of maternal condition on offspring performance in sockeye salmon Oncorhynchus nerka - K. B. Tierney; D. A. Patterson; C. J. Kennedy (Journal of Fish Biology, 2009)
Eggs were taken from adult sockeye salmon Oncorhynchus nerka that had reached their journey's end in spawn‐ready and moribund condition, and fertilized by healthy males. Egg number, size, hatching success and offspring growth did not differ with maternal condition, which suggests the absence of any persisting physiological maternal effects. Differences were noted in the swimming behaviour and physiology of the offspring at parr stage. In a 30 min schooling test conducted using groups of five in a flume, parr from moribund females were more likely to fatigue, were not as tightly schooled, and had a diminished startle response, both in the per cent responding and the burst distance. In individual, confined swimming tests conducted within a tube, post‐exercise plasma lactate concentration, which is an indicator of white muscle use, was greater for parr from moribund adult females. The moribund females also had elevated lactate following exercise (their migration), which suggests heritable differences may exist in muscle use. This study shows that juvenile O. nerka artificially propagated from females exhausted by their return migration can exhibit swimming performance differences, indicating that maternal condition may need to be considered in breeding programmes.

Toward a Rational Exuberance for Ecosystem Services Markets - Jeffrey D. Kline; Marisa J. Mazzotta; Trista M. Patterson (Journal of Forestry, 2009)
Ecosystem services markets have become a popular topic among environmental policymakers and ecosystem protection advocates. Their proponents view markets as a promising new way to finance conservation of threatened ecosystems worldwide at a time when the need for additional protection seems especially critical. Their advocates in forestry promise that such markets will soon offer new financial opportunities to forest landowners to augment or even replace income from the sale of timber, thereby increasing financial incentives for landowners to retain land in forests. But what is the real promise in ecosystem services markets and what can realistically be achieved by their implementation? We provide an overview of how environmental markets work in theory and discuss several issues that influence how effective they can be. We conclude that the promise of ecosystem services markets greatly depends on the particular circumstances of program implementation, including what services are to be traded and whether they are amenable to trading, the ability to enact and enforce regulation sufficient to induce trading, and how expected program results compare with those likely to arise from other conservation policy approaches.

Physiological, energetic and behavioural correlates of successful fishway passage of adult sockeye salmon Oncorhynchus nerka in the Seton River, British Columbia - L. B. Pon; S. G. Hinch; S. J. Cooke; D. A. Patterson; A. P. Farrell (Journal of Fish Biology, 2009)
Electromyogram (EMG) radio telemetry was used in conjunction with physiological biopsy to relate prior physiological condition and subsequent swimming energetics and behaviours to passage success of 13 wild adult sockeye salmon Oncorhynchus nerka at a vertical‐slot fishway on the Seton River, British Columbia. At the time of capture, plasma lactate, glucose and cortisol levels indicated that fish were not exhibiting unusually high levels of physiological stress. Very few differences existed between successful and unsuccessful fish in body size, initial plasma physiology and energy state and mean swim speed and energy use during passage. Generally, fish did not employ burst swimming during successful or failed attempts at passage, indicating that failure was probably not related to metabolic acidosis. Plasma Na + concentration was significantly lower in unsuccessful fish ( P O. nerka . Nevertheless, six of 13 fish failed to reascend the fishway and remained in the tailrace of the dam for more than a day on average before moving downstream and away from the dam. During this time, fish were observed actively seeking a means of passage, suggesting that there may have been other, undetermined causes of passage failure.

Cold shock and fish - M. R. Donaldson; S. J. Cooke; D. A. Patterson; J. S. Macdonald (Journal of Fish Biology, 2008)
Rapid decreases in water temperature may result in a number of physiological, behavioural and fitness consequences for fishes termed ‘cold shock’. Cold‐shock stress occurs when a fish has been acclimated to a specific water temperature or range of temperatures and is subsequently exposed to a rapid decrease in temperature, resulting in a cascade of physiological and behavioural responses and, in some cases, death. Rapid temperature decreases may occur from either natural ( e.g. thermocline temperature variation, seiches and storm events) or anthropogenic sources ( e.g. varied thermal effluents from power generation and production industries). The magnitude, duration and frequency of the temperature change as well as the initial acclimation temperatures of individuals can influence the extent of the consequences of cold shock on fishes. Early research on cold shock focused on documenting mortality events associated with cold shock. However, in recent years, a shift in research has occurred where the focus of cold‐shock studies now involves characterizing the sublethal effects of cold shock in terms of the stress response in fishes. This shift has revealed that cold shock can actually be used as a tool for fisheries science ( e.g. to induce polyploidy). The cold‐shock stress response offers opportunities to develop many exciting research questions, yet to date, cold‐shock research has been largely unfocused. Few studies attempt to link laboratory physiology experiments with ecologically relevant field data on behaviour, growth, bioenergetics and fitness. Additional research will allow for the development of more focused and robust management policies and conservation initiatives. This review synthesizes the sublethal physiological and behavioural consequences of cold‐shock stress on fishes, identifies natural and anthropogenic sources of cold shock, discusses the benefits of cold shock to fisheries science and describes mitigation and management efforts. Existing knowledge gaps and opportunities for future cold‐shock research are presented.

Effects of diluted Kraft pulp mill effluent on hybrid poplar and soil chemical properties - S. J. Patterson; D. S. Chanasyk; E. Mapfumo; M. A. Naeth (Irrigation Science, 2008)

The conspecific nature of eastern and red wolves: conservation and management implications - C. J. Kyle; A. R. Johnson; B. R. Patterson; P. J. Wilson; B. N. White (Conservation Genetics, 2008)

Jack Edgar Myers (1913–2006), an algal physiologist par excellence - Jerry J. Brand; David W. Krogmann; C. O. Patterson (Photosynthesis Research, 2008)

Vitamin E and selenium supplementation and risk of prostate cancer in the Vitamins and lifestyle (VITAL) study cohort - Ulrike Peters; Alyson J. Littman; Alan R. Kristal; Ruth E. Patterson; John D. Potter; Emily White (Cancer Causes & Control, 2008)

Behaviour and physiology of sockeye salmon homing through coastal waters to a natal river - Glenn T. Crossin; Scott G. Hinch; Steven J. Cooke; David W. Welch; Sonia D. Batten; David A. Patterson; Glen Van Der Kraak; J. Mark Shrimpton; Anthony P. Farrell (Marine Biology, 2007)

Impact of the 2005 coral bleaching event on Porites porites and Colpophyllia natans at Tektite Reef, US Virgin Islands - K. R. T. Whelan; J. Miller; O. Sanchez; M. Patterson (Coral Reefs, 2007)

Changes of Sorghum bicolor landrace diversity and farmers’ selection criteria over space and time, Ethiopia - Awegechew Teshome; Daniel Patterson; Zemede Asfew; J. Kenneth Torrance; John T. Arnason (Genetic Resources and Crop Evolution, 2007)

The use of hydrologic and Ecological indicators for the restoration of drainage ditches and water diversions in a Mountain Fen, Cascade Range, California - Lindsay Patterson; David J. Cooper (Wetlands, 2007)

Paleoecological Assessment of Watershed History in PRIMENet Watersheds at Acadia National Park, USA - M. Schauffler; S. J. Nelson; J. S. Kahl; G. L. Jacobson; T. A. Haines; W. A. Patterson; K. B. Johnson (Environmental Monitoring and Assessment, 2007)

Distribution of specific tetracycline and erythromycin resistance genes in environmental samples assessed by macroarray detection - Andrea J. Patterson; Roberto Colangeli; Patrizia Spigaglia; Karen P. Scott (Environmental Microbiology, 2007)
Summary A macroarray system was developed to screen environmental samples for the presence of specific tetracycline (Tc R ) and erythromycin (erm R ) resistance genes. The macroarray was loaded with polymerase chain reaction (PCR) amplicons of 23 Tc R genes and 10 erm R genes. Total bacterial genomic DNA was extracted from soil and animal faecal samples collected from different European countries. Macroarray hybridization was performed under stringent conditions and the results were analysed by fluorescence scanning. Pig herds in Norway, reared without antibiotic use, had a significantly lower incidence of antibiotic resistant bacteria than those reared in other European countries, and organic herds contained lower numbers of resistant bacteria than intensively farmed animals. The relative proportions of the different genes were constant across the different countries. Ribosome protection type Tc R genes were the most common resistance genes in animal faecal samples, with the tet (W) gene the most abundant, followed by tet (O) and tet (Q). Different resistance genes were present in soil samples, where erm (V) and erm (E) were the most prevalent followed by the efflux type Tc R genes. The macroarray proved a powerful tool to screen DNA extracted from environmental samples to identify the most abundant Tc R and erm R genes within those tested, avoiding the need for culturing and biased PCR amplification steps.

Long-term Evaluation of a Composite Cover Overlaying a Sulfidic Tailings Facility - B. M. Patterson; B. S. Robertson; R. J. Woodbury; B. Talbot; G. B. Davis (Mine Water and the Environment, 2006)

Decibel Attenuation of Pulsed Electromagnetic Field (PEMF) in Blood and Cortical Bone Determined Experimentally and from the Theory of Ohmic Losses - Maciej Zborowski; Boris Kligman; Ronald J. Midura; Alan Wolfman; Thomas E. Patterson; Michael Ibiwoye; Mark Grabiner (Annals of Biomedical Engineering, 2006)

Elemental signatures of Acanthochromis polyacanthus otoliths from the Great Barrier Reef have significant temporal, spatial, and between-brood variation - Heather M. Patterson; Michael J. Kingsford (Coral Reefs, 2005)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Impact of Soil Amendments on Broccoli Quality and Napropamide Movement Under Field Conditions - G. F. Antonious; M. A. Patterson; J. C. Snyder (Bulletin of Environmental Contamination and Toxicology, 2005)

Resolution of the early life history of a reef fish using otolith chemistry - Heather M. Patterson; Michael J. Kingsford; Malcolm T. McCulloch (Coral Reefs, 2005)

Molecular genetic variation across the southern and eastern geographic ranges of the African lion, Panthera leo - Jean Dubach; B. D. Patterson; M. B. Briggs; K. Venzke; J. Flamand; P. Stander; L. Scheepers; R. W. Kays (Conservation Genetics, 2005)

Brain mitochondrial injury in human immunodeficiency virus–seropositive (HIV+) individuals taking nucleoside reverse transcriptase inhibitors - Brian C Schweinsburg; Michael J Taylor; Omar M Alhassoon; Raul Gonzalez; Gregory G Brown; Ronald J Ellis; Scott Letendre; John S Videen; J Allen McCutchan; Thomas L Patterson; Igor Grant; the HNRC Group (Journal of NeuroVirology, 2005)

Comparison of 1-hydroxypyrene exposure in the US population with that in occupational exposure studies - Wenlin Huang; James Grainger; Donald G. Patterson; Wayman E. Turner; Samuel P. Caudill; Larry L. Needham; James L. Pirkle; Eric J. Sampson (International Archives of Occupational and Environmental Health, 2004)

Model-Based Inference of Recombination Hotspots in a Highly Variable Oncogene - G. Greenspan; D. Geiger; F. Gotch; M. Bower; S. Patterson; M. Nelson; B. Gazzard; J. Stebbing (Journal of Molecular Evolution, 2004)

Cold-water acclimation does not modify whole-body fluid regulation during subsequent cold-water immersion - J. M. Stocks; M. J. Patterson; D. E. Hyde; A. B. Jenkins; K. D. Mittleman; N. A. S. Taylor (European Journal of Applied Physiology, 2004)

The reproducibility of closed-pouch sweat collection and thermoregulatory responses to exercise?heat stress - Gavin Hayden; Helen C. Milne; Mark J. Patterson; Myra A. Nimmo (European Journal of Applied Physiology, 2004)

Late Holocene lake level dynamics inferred from magnetic susceptibility and stable oxygen isotope data: Lake Elsinore, southern California (USA) - Matthew E. Kirby; Christopher J. Poulsen; Steve P. Lund; William P. Patterson; Liam Reidy; Douglas E. Hammond (Journal of Paleolimnology, 2004)

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Recombination Does Not Occur in Newly Identified Diverged Oceanic Picornaviruses - G. Greenspan; D. Geiger; F. Gotch; M. Bower; S. Patterson; M. Nelson; B. Gazzard; J. Stebbing (Journal of Molecular Evolution, 2004)

Model-Based Inference of Recombination Hotspots in a Highly, Variable Oncogene - G. Greenspan; D. Geiger; F. Gotch; M. Bower; S. Patterson; M. Nelson; B. Gazzard; J. Stebbing (Journal of Molecular Evolution, 2004)

VARIABILITY IN THE DIET OF HARBOR PORPOISES ( PHOCOENA PHOCOENA ) IN SCOTTISH WATERS 1992–2003 - M. B. Santos; G. J. Pierce; J. A. Learmonth; R. J. Reid; H. M. Ross; I. A. P. Patterson; D. G. Reid; D. Beare (Marine Mammal Science, 2004)
A bstract Interannual, seasonal, and regional variation in the diet of porpoises, Phocoena phocoena , in Scottish (UK) waters was studied using stomach contents of animals stranded between 1992 and 2003. Most samples came from the east coast (including many porpoises killed by bottlenose dolphins), with smaller numbers from the west coast and from Shetland. The most important prey types, in terms of contribution by number and mass, were whiting ( Merlangius merlangus ) and sand eels (Ammodytidae). Multivariate analysis confirmed the existence of regional, seasonal, and interannual variation in diet, as well as differences ( i. e. , biases) related to cause of death. These differences were further explored using univariate analyses. Sand eels were more important in the summer months (quarters 2 and 3) and on the east coast, whereas gadids were more important in winter and in the Shetland area. Some, but not all, observed trends in the numerical importance and size of prey taken were consistent with trends in abundance and size of fish taken during research trawl surveys. There was some evidence that porpoises Clupea harengus and sprat Sprattus sprattus ) formed a relatively small proportion of the diet, but their importance varied from year to year. Although possible methodological biases prevent firm conclusions, it appears that the importance of clupeids in porpoise diet may have decreased since the 1960s, mirroring the decline in North Sea herring abundance. The recovery of the North Sea herring stock in recent years is not as yet reflected in porpoise diet.

Pesticide Residues in Soil and Quality of Potato Grown with Sewage Sludge - G. F. Antonious; M. A. Patterson; J. C. Snyder (Bulletin of Environmental Contamination and Toxicology, 2003)

Letters - C.P. Patterson; B. Daniels; N.R. Bosic; J. Coufal; M. Stevens (Journal of Forestry, 2003)

Free-living heterotrophic euglenids from freshwater sites in mainland Australia - Sabrina Schroeckh; Won Je Lee; David J. Patterson (Hydrobiologia, 2003)

Magnetic Field Visualization in Applications to Pulsed Electromagnetic Field Stimulation of Tissues - Maciej Zborowski; Ronald J. Midura; Alan Wolfman; Thomas Patterson; Michael Ibiwoye; Yoshi Sakai; Mark Grabiner (Annals of Biomedical Engineering, 2003)

Impedance cardiographic measurement of the physiological response to the Valsalva manoeuvre - R. P. Patterson; J. Zhang (Medical & Biological Engineering & Computing, 2003)

Effects of Dietary Exposure to Environmentally Relevant Concentrations of Weathered Prudhoe Bay Crude Oil in Ranch-Raised Mink ( Mustela vison ) - K. J. Beckett; R. J. Aulerich; L. K. Duffy; J. S. Patterson; S. J. Bursian (Bulletin of Environmental Contamination and Toxicology, 2002)

Serum selenium and the risk of cervical cancer among women in the United States - Frances E. Thompson; Blossom H. Patterson; Stephanie J. Weinstein; Mary McAdams; Vickie L. Spate; Richard F. Hamman; Robert S. Levine; Katherine Mallin; Paul D. Stolley; Louise A. Brinton; J. Steven Morris; Regina G. Ziegler (Cancer Causes & Control, 2002)

Opponent and nonopponent contributions to the zebrafish electroretinogram using heterochromatic flicker photometry - W. Patterson; A. McDowell; A. Hughes; J. Bilotta (Journal of Comparative Physiology A, 2002)

Understanding the biochemical activities of galectin-1 and galectin-3 in the nucleus - Ronald J. Patterson; Weizhong Wang; John L. Wang (Glycoconjugate Journal, 2002)

Quantitative assessment of coral diseases in the Florida Keys: strategy and methodology - D.L. Santavy; E. Mueller; E.C. Peters; L. MacLaughlin; J.W. Porter; K.L. Patterson; J. Campbell (Hydrobiologia, 2001)

The Diagnosis and Recommendation Integrated System (DRIS) for diagnosing the nutrient status of grassland swards: III Practical applications - J. S. Bailey; R. A. Dils; R. H. Foy; D. Patterson (Plant and Soil, 2000)

Weeds, Insects, and Diseases - D.T. Patterson; J.K. Westbrook; R.J.V. Joyce†; P.D. Lingren; J. Rogasik (Climatic Change, 1999)

Centrin in the groove: immunolocalisation of centrin and microtubules in the putatively primitive protistChilomastix cuspidata (Retortamonadida) - N. D. Weerakoon; J. D. I. Harper; A. G. B. Simpson; D. J. Patterson (Protoplasma, 1999)

Assessment of a Sr isotope vital effect (87Sr/86Sr) in marine taxa from Lee Stocking Island, Bahamas - E. G. Reinhardt; J. Blenkinsop; R. T. Patterson (Geo-Marine Letters, 1998)

A fluorescence double-quenching study of native lipoproteins in an animal model of manganese deficiency - Paul N. Taylor; Howard H. Patterson; Dorothy J. Klimis-Tavantzis (Biological Trace Element Research, 1997)

Effects of artificially-induced anaemia on sudomotor and cutaneous blood flow responses to heat stress - Nigel A. S. Taylor; Mark J. Patterson; James D. Cotter; Duncan J. Macfarlane (European Journal of Applied Physiology, 1997)

Vitamin supplements and cancer risk: the epidemiologic evidence - R. E. Patterson; E. White; A. R. Kristal; M. L. Neuhouser; J. D. Potter (Cancer Causes & Control, 1997)

Sweat distribution before and after repeated heat exposure - James D. Cotter; Mark J. Patterson; Nigel A. S. Taylor (European Journal of Applied Physiology, 1997)

Heterotrophic flagellates, centrohelid heliozoa and filose amoebae from marine and freshwater sites in the Antarctic - S. Tong; N. Vørs; D. J. Patterson (Polar Biology, 1997)

Expression of de novo high-lysine α-helical coiled-coil proteins may significantly increase the accumulated levels of lysine in mature seeds of transgenic tobacco plants - Sharon J. Keeler; Cathy L. Maloney; Patricia Y. Webber; Carole Patterson; Lee T. Hirata; S. Carl Falco; Janet A. Rice (Plant Molecular Biology, 1997)

Trophic effects of sponge feeding within Lake Baikal's littoral zone. 2. Sponge abundance, diet, feeding efficiency, and carbon flux - Adele J. Pile; Mark R. Patterson; Michael Savarese; Valeri I. Chernykh; Vladimir A. Fialkov (Limnology and Oceanography, 1997)
Endemic freshwater demosponges in the littoral zone of Lake Baikal, Russia, dominate the benthic biomass, covering 44% of the benthos. We measured in situ sponge abundance and grazing and calculated sponge‐mediated fluxes of picoplankton (plankton µ m) for two common species, Baikalospongia intermedia and Baikalospongia bacillifera. By means of dual‐beam flow cytometry, we found retention efficiencies ranging from 58 to 99% for four types of picoplankton: heterotrophic bacteria, Synechococcus‐type cyanobacteria, autotrophic picoplankton with one chloroplast, and autotrophic picoplankton with two chloroplasts. By using a general model for organism‐mediated fluxes, we conservatively estimate that through active suspension feeding, sponges are a sink for 1.97 g C d −1 m −2 , mostly from procaryotic cell types. Furthermore, grazing by these extensive sponge communities can create a layer of picoplankton‐depleted water overlying the benthic community in this unique lake.

Drosophila purine auxotrophy: New alleles ofadenosine2 exhibiting a complex visible phenotype - S. Y. K. Tiong; C. Keizer; D. Nash; J. Bleskan; D. Patterson (Biochemical Genetics, 1989)

Correlation between serum and adipose tissue levels of 2,3,7,8-tetrachlorodibenzo-p-dioxin in 50 persons from Missouri - D. G. Patterson; L. L. Needham; J. L. Pirkle; D. W. Roberts; J. Bagby; W. A. Garrett; J. S. Andrews; H. Falk; J. T. Bernert; E. J. Sampson; V. N. Houk (Archives of Environmental Contamination and Toxicology, 1988)

Applications of immunogold labelling in animal and plant virology - S. Patterson; B. J. M. Verduin (Archives of Virology, 1987)

Analysis of antigenic determinants on internal and external proteins of influenza virus and identification of antigenic subpopulations of virions in recent field isolates using monoclonal antibodies and immunogold labelling - S. Patterson; J. S. Oxford (Archives of Virology, 1986)

Structure elucidation of some minor components of the polybromobiphenyl mixture, Firemaster - Donna L. Orti; Robert H. Hill; Donald G. Patterson; Larry L. Needham; Renate D. Kimbrough; Cynthia C. Alley; Hsing -Chung J. Lee (Archives of Environmental Contamination and Toxicology, 1983)

Song repertoires and sexual selection in the Red-winged Blackbird - K. Yasukawa; J. L. Blank; C. B. Patterson (Behavioral Ecology and Sociobiology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

A new fla gene in Salmonella typhimurium?flaR?and its mutant phenotype-superhooks - Judith Patterson-Delafield; Rafael J. Martinez; B. A. D. Stocker; S. Yamaguchi (Archives of Microbiology, 1973)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)